Tire

The tire's multi-layered tread design with lignin-based materials in both the surface and inner rubber layers addresses the issue of steering stability on dry roads, enhancing force transmission and overall handling.

JP2025065795APending Publication Date: 2025-04-22SUMITOMO RUBBER INDUSTRIES LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2023175241
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-10-10
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

Existing tires lack sufficient steering stability on dry road surfaces, which is crucial for safety and performance.

Method used

A tire with a multi-layered tread portion consisting of a surface rubber layer and at least one inner rubber layer, both containing lignin-based materials, where the content of lignin-based material in the surface rubber layer is less than in the inner rubber layer, optimizing the force transmission during turning.

Benefits of technology

The tire achieves enhanced steering stability on dry road surfaces by improving force generation and transmission within the tread portion, leading to better handling and safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025065795000003
    Figure 2025065795000003
  • Figure 2025065795000004
    Figure 2025065795000004
  • Figure 2025065795000001
    Figure 2025065795000001
Patent Text Reader

Abstract

To provide a tire excellent in driving stability on a dry road surface.SOLUTION: A tire includes a multilayer structure tread part composed of a surface rubber layer and at least one inner rubber layer disposed inside the surface rubber layer in a tire radial direction. At least one of the surface rubber layer and the inner rubber layer includes a lignin material. The content Lc (pts.mass) of the lignin material with respect to 100 pts.mass of the rubber constituent of the surface rubber layer is less than the content Lb (pts.mass) of the lignin material with respect to 100 pts.mass of the rubber constituent of the inner rubber layer containing the lignin material.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a tire. [Background technology]

[0002] From the viewpoint of safety, tires are required to have driving stability and the like. Summary of the Invention [Problem to be solved by the invention]

[0003] An object of the present invention is to solve the above problems and to provide a tire that has excellent driving stability on dry road surfaces. [Means for solving the problem]

[0004] The present invention provides a tire having a multi-layered tread portion including a surface rubber layer and at least one inner rubber layer disposed radially inward of the surface rubber layer, the surface rubber layer and at least one of the inner rubber layers contain a lignin-based material; The tire relates to a tire in which the content Lc (parts by mass) of the lignin-based material per 100 parts by mass of the rubber component of the surface rubber layer is less than the content Lb (parts by mass) of the lignin-based material per 100 parts by mass of the rubber component of the inner rubber layer containing the lignin-based material. Effect of the Invention

[0005] The present invention provides a tire with a multi-layered tread portion consisting of a surface rubber layer and at least one inner rubber layer arranged radially inward of the surface rubber layer, wherein the surface rubber layer and at least one of the inner rubber layers contain a lignin-based material, and the content Lc (parts by mass) of the lignin-based material per 100 parts by mass of the rubber component of the surface rubber layer is less than the content Lb (parts by mass) of the lignin-based material per 100 parts by mass of the rubber component of the inner rubber layer containing the lignin-based material, thereby making it possible to provide a tire with excellent steering stability on dry road surfaces. [Brief description of the drawings]

[0006] [Figure 1] It is a cross-sectional view showing a part of a pneumatic tire. [Diagram 2] It is an enlarged cross-sectional view showing the vicinity of the multi-layer structure tread portion of the tire of FIG. 1.

Mode for Carrying Out the Invention

[0007] The present invention includes a multi-layer structure tread portion composed of a surface rubber layer and at least one inner rubber layer disposed on the inner side in the tire radial direction of the surface rubber layer, the surface rubber layer and the inner rubber layer containing a lignin-based material, and the content Lc of the lignin-based material in the surface rubber layer is less than the content Lb of the lignin-based material in the inner rubber layer containing the lignin-based material (Lc < Lb). It is a tire that satisfies the relationship.

[0008] The reason why the above-described effect is obtained by the tire is not necessarily clear, but it is presumed as follows. When a lignin-based material is blended in the tread portion, hydrogen bonds are generated between the lignins and interact with the rubber component as well, so that it becomes easy to generate and transmit force inside the rubber. In addition, since the lignin-based material amount Lc of the surface rubber layer and the lignin-based material amount Lb of the inner rubber layer satisfy Lc < Lb, force is generated from the inner side of the tread portion during turning, and a large force is likely to be generated. By blending a lignin-based material in both the surface rubber layer and the inner rubber layer of the tread portion, force is easily transmitted between the rubber layers. Therefore, it is presumed that the dry road surface handling stability is improved because it becomes easy to generate force inside the rubber layer of the tread portion and it becomes easy to transmit the force generated during turning also in the entire tread portion.

[0009] Thus, the present invention solves the problem (objective) of improving the handling stability on a dry road surface by adopting a configuration that satisfies the relationship of "Lc < Lb". That is, the parameter of "Lc < Lb" does not define the problem (objective). The problem of the present application is to improve the handling stability on a dry road surface, and for this purpose, the configuration is made to satisfy the said parameter.

[0010] The above tire includes a tread portion having a multilayer structure composed of a surface rubber layer and an inner rubber layer disposed on the inner side in the tire radial direction of the surface rubber layer.

[0011] In this specification, the surface rubber layer means the rubber layer on the outermost surface side in the tire radial direction among the rubber layers constituting the multilayer structure tread portion. The inner rubber layer means one or more rubber layers disposed on the inner side in the tire radial direction of the surface rubber layer among the rubber layers constituting the multilayer structure tread portion. For example, when the tread portion is composed of two rubber layers, the inner rubber layer is the rubber layer disposed adjacent to the inner side in the tire radial direction of the surface rubber layer. When the tread portion is composed of three or more rubber layers, the inner rubber layer is two or more rubber layers disposed on the inner side in the tire radial direction of the surface rubber layer. Among these rubber layers, it is sufficient that the content Lb of the lignin-based material in any rubber layer containing the lignin-based material and the content Lc of the lignin-based material in the surface rubber layer satisfy Lc < Lb, and it is also possible that the content Lb of the lignin-based material in each of the two or more rubber layers and the content Lc of the lignin-based material in the surface rubber layer satisfy Lc < Lb.

[0012] The multi-layer tread portion can use any two or more layers of treads, including two-layer treads, three-layer treads, and treads with a structure of four or more layers. For example, in the case of a three-layer tread, the outermost rubber layer (the first layer) of the tread portion constitutes the surface rubber layer, and the rubber layer (the second layer) arranged adjacent to the inner side in the tire radius direction of the surface rubber layer constitutes an inner rubber layer satisfying Lc < Lb, the rubber layer (the third layer) arranged adjacent to the inner side in the tire radius direction of the second layer constitutes an inner rubber layer satisfying Lc < Lb, or any form in which both the rubber layers of the second layer and the third layer constitute inner rubber layers satisfying Lc < Lb may be used. Among these, from the perspective of obtaining more effects, a form in which the lignin-based material content of the first layer < the lignin-based material content of the second layer is preferable, and a form in which the lignin-based material content of the first layer < the lignin-based material content of the second layer < the lignin-based material content of the third layer is more preferable.

[0013] In the above tire, the surface rubber layer is composed of a surface rubber layer composition, and the inner rubber layer is composed of an inner rubber layer composition.

[0014] Hereinafter, materials that can be commonly used in the surface rubber layer composition and the inner rubber layer composition will be described.

[0015] The surface rubber layer composition and the inner rubber layer composition contain a rubber component. Here, the rubber component is a component that contributes to cross-linking. Generally, a polymer with a weight average molecular weight (Mw) of 10,000 or more and a polymer component that is not extracted by acetone corresponds to the rubber component. The elastomer component is in a solid state at normal temperature (25°C).

[0016] The weight average molecular weight of the rubber component is preferably 50,000 or more, more preferably 150,000 or more, still more preferably 200,000 or more, particularly preferably 270,000 or more, and is also preferably 2,000,000 or less, more preferably 1,500,000 or less, still more preferably 1,000,000 or less. When within the above range, there is a tendency to obtain better effects.

[0017] In this specification, the weight average molecular weight (Mw) and number average molecular weight (Mn) can be determined by standard polystyrene conversion based on the measured value by gel permeation chromatography (GPC) (GPC-8000 series manufactured by Tosoh Corporation, detector: differential refractometer, column: TSKGEL SUPERMULTIPORE HZ-M manufactured by Tosoh Corporation). In the case of a polymer having a modifying group, the modifying group interacts with the silica gel of the column, making it impossible to obtain accurate Mw and Mn, so that Mw and Mn are usually measured before carrying out the modification treatment.

[0018] The rubber components usable in the surface rubber layer composition and the inner rubber layer composition may be either unmodified rubber or modified rubber. The modified rubber may be a rubber having a functional group that interacts with a filler such as silica. For example, the modified rubber may be a terminal modified rubber (terminal modified rubber having the functional group at the terminal) in which at least one terminal of the rubber is modified with a compound (modifier) ​​having the functional group, a main chain modified rubber having the functional group at the main chain, a main chain terminal modified rubber having the functional group at the main chain and terminal (for example, a main chain terminal modified rubber having the functional group at the main chain and at least one terminal modified with the modifier), or a terminal modified rubber modified (coupled) with a polyfunctional compound having two or more epoxy groups in the molecule and having a hydroxyl group or an epoxy group introduced therein.

[0019] Examples of the functional group include an amino group, an amide group, a silyl group, an alkoxysilyl group, an isocyanate group, an imino group, an imidazole group, a urea group, an ether group, a carbonyl group, an oxycarbonyl group, a mercapto group, a sulfide group, a disulfide group, a sulfonyl group, a sulfinyl group, a thiocarbonyl group, an ammonium group, an imide group, a hydrazo group, an azo group, a diazo group, a carboxyl group, a nitrile group, a pyridyl group, an alkoxy group, a hydroxyl group, an oxy group, and an epoxy group. These functional groups may have a substituent. Among them, an amino group (preferably an amino group in which a hydrogen atom of an amino group is substituted with an alkyl group having 1 to 6 carbon atoms), an alkoxy group (preferably an alkoxy group having 1 to 6 carbon atoms), and an alkoxysilyl group (preferably an alkoxysilyl group having 1 to 6 carbon atoms) are preferred.

[0020] In the above-mentioned surface rubber layer composition and the above-mentioned inner rubber layer composition, examples of the rubber components that can be used include diene rubbers. Examples of diene rubbers include isoprene rubbers, butadiene rubbers (BR), styrene butadiene rubbers (SBR), styrene isoprene butadiene rubbers (SIBR), ethylene propylene diene rubbers (EPDM), chloroprene rubbers (CR), and acrylonitrile butadiene rubbers (NBR). Examples of the rubber components include butyl rubbers and fluororubbers. These may be used alone or in combination of two or more. These rubber components may be modified or hydrogenated, and extended rubbers extended with oil, resin, liquid rubber components, and the like may be used.

[0021] The raw materials (monomers) of synthetic rubbers such as SBR and BR may be derived from petroleum or may be recycled from rubber products such as tires or non-rubber products such as polystyrene. Monomers obtained by recycling (recycled monomers) are not particularly limited, and include recycled butadiene and recycled aromatic vinyl. Examples of the butadiene include 1,2-butadiene and 1,3-butadiene. Examples of the aromatic vinyl include, but are not particularly limited, styrene. Among them, it is preferable to use recycled butadiene (recycled butadiene) and / or recycled styrene (recycled styrene) as the raw materials.

[0022] The method for producing the recycled monomer is not particularly limited, and examples thereof include synthesis from recycle-derived naphtha obtained by decomposing rubber products such as tires. The method for producing the recycled naphtha is also not particularly limited, and examples thereof include decomposing rubber products such as tires under high temperature and pressure, decomposing with microwaves, or mechanically crushing and then extracting.

[0023] Furthermore, the raw material (monomer) of synthetic rubber such as SBR and BR may be derived from biomass. Examples of the monomer derived from biomass (biomass monomer) include, but are not limited to, butadiene derived from biomass and aromatic vinyl derived from biomass. Examples of the butadiene include 1,2-butadiene and 1,3-butadiene. Examples of the aromatic vinyl include, but are not limited to, styrene. In addition, the method for producing the biomass monomer is not particularly limited, and examples thereof include biological and / or chemical and / or physical conversion of animals and plants. A representative example of biological conversion is fermentation by a microorganism, and examples of chemical and / or physical conversion include those using a catalyst, those using high heat, those using high pressure, those using electromagnetic waves, those using critical liquids, and combinations thereof. Examples of biomass sources for these monomers include sugar, wood, plant residues after useful components are obtained, plant-derived ethanol, biomass naphtha, etc.

[0024] The polymer (biomass polymer) synthesized from a biomass monomer component is not particularly limited, and examples thereof include polybutadiene rubber synthesized from butadiene derived from biomass, aromatic vinyl / butadiene copolymer synthesized from butadiene derived from biomass and / or aromatic vinyl derived from biomass, etc. Examples of the aromatic vinyl / butadiene copolymer include styrene butadiene rubber synthesized from butadiene derived from biomass and / or styrene derived from biomass.

[0025] Whether the raw material for a polymer is biomass-derived can be determined by the percent modern carbon (pMC) measured in accordance with ASTM D6866-10.

[0026] pMC stands for modern standard reference carbon. 14 C concentration vs. sample 14 This is the ratio of the carbon concentration to the biomass concentration of the compound (rubber), and this value is used as an index of the biomass ratio of the compound (rubber). The significance of this value is described below.

[0027] 1 mole of carbon atoms (6.02 × 10 23 ) contains approximately 6.02 × 10 atoms, which is about one trillionth of the size of a normal carbon atom. 11 pcs 14 C exists. 14 C is called a radioisotope, and its half-life is 5,730 years, and it decreases regularly. It takes 226,000 years for all of them to decay. Therefore, in fossil fuels such as coal, oil, and natural gas, which are thought to have been absorbed and fixed by plants and other organisms more than 226,000 years ago, C was also included in these when they were first fixed. 14 All C elements have decayed. Therefore, in the 21st century, fossil fuels such as coal, oil, and natural gas are 14 There is no C element at all. Therefore, chemical substances produced using these fossil fuels as raw materials also 14 It does not contain any C elements.

[0028] on the other hand, 14 C is produced continuously by nuclear reactions in the atmosphere caused by cosmic rays, and this is balanced by the loss of C due to radioactive decay. In the Earth's atmospheric environment, 14 The amount of C is constant. Therefore, the amount of biomass-derived materials circulating in the current environment is 14 As mentioned above, the C concentration is about 1×10 -12 The value is about mol%. Therefore, by using the difference between these values, it is possible to calculate the ratio (biomass ratio) of compounds derived from natural resources (compounds derived from biomass resources) in a certain compound (rubber).

[0029] this 14 C is typically measured as follows: using accelerator mass spectrometry based on a tandem accelerator, 13 C concentration ( 13 C / 12 C). 14 C concentration ( 14 C / 12 C) is measured. 14 The modern standard reference for the C concentration is the carbon circulating in nature in 1950. 14 The specific standard substance used is the oxalic acid standard provided by NIST (National Institute of Standards and Technology). The specific radioactivity of carbon in this oxalic acid (per gram of carbon) is 14 C) for each carbon isotope, 13 The standard value is the value corrected for decay from 1950 to the measurement date, with C corrected to a constant value. 14 This is used as the C concentration value (100%). The ratio of this value to the value actually measured for the sample is the pMC value.

[0030] Therefore, if rubber is made from 100% biomass (natural) derived materials, it will show a value of approximately 110 pMC, although there may be regional differences (currently, under normal conditions, it is often not 100). On the other hand, for chemical substances derived from petroleum and other fossil fuels, 14 When the C concentration is measured, it will show approximately 0 pMC (for example, 0.3 pMC). This value corresponds to the biomass ratio of 0% mentioned above.

[0031] For these reasons, it is preferable in terms of environmental protection to use a material such as rubber having a high pMC value, that is, a material such as rubber having a high biomass ratio, in a rubber composition.

[0032] Among these, from the viewpoint of obtaining a better effect, the surface rubber layer composition preferably contains an isoprene-based rubber, more preferably contains an isoprene-based rubber, and BR and / or SBR, and further preferably contains an isoprene-based rubber, BR and SBR. The composition for the inner rubber layer preferably contains at least one of an isoprene-based rubber and BR, and more preferably contains an isoprene-based rubber and BR.

[0033] Although the mechanism by which the inner rubber layer composition containing the lignin-based material is more effective when it contains isoprene-based rubber is unclear, it is believed that the isoprene-based rubber is more rigid when a lignin-based material containing an OH group is blended with the isoprene-based rubber, and therefore the effect is more likely to be obtained. Therefore, it is presumed that the steering stability on dry road surfaces is significantly improved.

[0034] Examples of isoprene-based rubber include natural rubber (NR), isoprene rubber (IR), modified NR, modified NR, and modified IR. Examples of NR include SIR20, RSS♯3, TSR20, and other rubber industry-standard rubbers. Examples of IR include IR2200 and other rubber industry-standard rubbers. Examples of modified NR include deproteinized natural rubber (DPNR), high-purity natural rubber (UPNR), and other rubbers. Examples of modified NR include epoxidized natural rubber (ENR), hydrogenated natural rubber (HNR), and grafted natural rubber. Examples of modified IR include epoxidized isoprene rubber, hydrogenated isoprene rubber, and grafted isoprene rubber. These may be used alone or in combination of two or more.

[0035] In the above-mentioned surface rubber layer composition, the content of the isoprene-based rubber in 100% by mass of the rubber component is preferably 5% by mass or more, more preferably 20% by mass or more, even more preferably 30% by mass or more, and is preferably 70% by mass or less, more preferably 50% by mass or less, even more preferably 40% by mass or less. When it is within the above range, the effect tends to be better obtained.

[0036] In the composition for the inner rubber layer, the content of the isoprene-based rubber in 100% by mass of the rubber component is preferably 40% by mass or more, more preferably 60% by mass or more, and even more preferably 70% by mass or more, and is preferably 95% by mass or less, more preferably 85% by mass or less, and even more preferably 80% by mass or less. Within the above ranges, the effect tends to be better obtained.

[0037] The BR is not particularly limited, and for example, high cis BR with a high cis content, BR containing syndiotactic polybutadiene crystals, BR synthesized using a rare earth catalyst (rare earth BR), etc. can be used. These may be used alone or in combination of two or more. In particular, the BR preferably contains high cis BR with a cis content of 90% by mass or more. The cis content is more preferably 95% by mass or more. The cis content can be measured by infrared absorption spectroscopy.

[0038] The cis amount of BR means the cis amount of the BR when there is one type of BR, and means the average cis amount when there are multiple types of BR. The average cis content of BR can be calculated by {Σ(content of each BR × cis content of each BR)} / total content of all BRs. For example, when 100% by mass of the rubber component contains 20% by mass of BR with a cis content of 90% by mass and 10% by mass of BR with a cis content of 40% by mass, the average cis content of BR is 73.3% by mass (=(20×90+10×40) / (20+10)).

[0039] In addition, either unmodified or modified BR can be used as the BR. Modified BR includes modified BR in which the same functional group as that of modified rubber is introduced. In addition, hydrogenated butadiene polymer (hydrogenated BR) can also be used as the BR.

[0040] In the above-mentioned surface rubber layer composition, the content of BR in 100% by mass of the rubber component is preferably 5% by mass or more, more preferably 20% by mass or more, even more preferably 30% by mass or more, and is preferably 70% by mass or less, more preferably 50% by mass or less, even more preferably 40% by mass or less. Within the above ranges, the effect tends to be better obtained.

[0041] In the composition for the inner rubber layer, the content of BR in 100% by mass of the rubber component is preferably 5% by mass or more, more preferably 20% by mass or more, and even more preferably 30% by mass or more, and is preferably 70% by mass or less, more preferably 50% by mass or less, and even more preferably 40% by mass or less. Within the above ranges, the effect tends to be better obtained.

[0042] The SBR is not particularly limited, and for example, emulsion polymerized styrene butadiene rubber (E-SBR), solution polymerized styrene butadiene rubber (S-SBR), etc. can be used. These may be used alone or in combination of two or more kinds.

[0043] The styrene content of SBR is preferably 5% by mass or more, more preferably 20% by mass or more, and even more preferably 23.5% by mass or more. The styrene content is preferably 60% by mass or less, more preferably 40% by mass or less, and even more preferably 35% by mass or less. Within the above range, the effect tends to be better obtained. In this specification, the styrene content is 1 It can be measured by H-NMR measurement.

[0044] The styrene amount of SBR means the styrene amount of the SBR when there is one type of SBR, and means the average styrene amount when there are multiple types of SBR. The average styrene amount of SBR can be calculated by {Σ(content of each SBR × styrene amount of each SBR)} / total content of all SBRs. For example, when 100% by mass of the rubber component contains 85% by mass of SBR with a styrene amount of 40% by mass and 5% by mass of SBR with a styrene amount of 25% by mass, the average styrene amount of the SBR is 39.2% by mass (=(85×40+5×25) / (85+5)).

[0045] The vinyl bond content of SBR is preferably 30% by mass or more, more preferably 40% by mass or more, and even more preferably 50% by mass or more. When the vinyl bond content is within the above range, preferably 70% by mass or less, more preferably 65% ​​by mass or less, and even more preferably 60% by mass or less, the effect tends to be better. In this specification, the vinyl bond amount (1,2-bonded butadiene unit amount) can be measured by infrared absorption spectroscopy.

[0046] The vinyl content of SBR (amount of 1,2-bonded butadiene units) is the proportion of vinyl bonds when the total mass of the butadiene parts in SBR is taken as 100 (unit: mass%), and is calculated as vinyl content [mass%] + cis content [mass%] + trans content [mass%] = 100 [mass%]. When there is one type of SBR, it means the vinyl content of that SBR, and when there are multiple types, it means the average vinyl content. The average vinyl content of SBR can be calculated by Σ{content of each SBR × (100 [mass%] - styrene content of each SBR [mass%]) × vinyl content of each SBR [mass%]} / Σ{content of each SBR × (100 [mass%] - styrene content of each SBR [mass%])}. For example, in 100 parts by mass of the rubber component, there are 75 parts by mass of SBR with a styrene content of 40 mass% and a vinyl content of 30 mass%, 25 parts by mass of styrene, and 10 parts by mass of vinyl. In the case where SBR with a vinyl content of 20 mass% is 15 parts by mass and the remaining 10 parts by mass is a component other than SBR, the average vinyl content of the SBR is 28 mass% (={75 × (100 [mass%] - 40 [mass%]) × 30 [mass%] + 15 × (100 [mass%] - 25 [mass%]) × 20 [mass%])} / {75 × (100 [mass%] - 40 [mass%]) + 15 × (100 [mass%] - 25 [mass%])}.

[0047] Both unmodified and modified SBR can be used. Modified SBR includes modified SBR with the same functional groups as modified rubber. Hydrogenated styrene-butadiene copolymer (hydrogenated SBR) can also be used as SBR.

[0048] In the above-mentioned surface rubber layer composition, the content of SBR in 100% by mass of the rubber component is preferably 15% by mass or more, more preferably 30% by mass or more, even more preferably 40% by mass or more, and is preferably 80% by mass or less, more preferably 60% by mass or less, even more preferably 50% by mass or less. Within the above ranges, the effect tends to be better obtained.

[0049] In the composition for the inner rubber layer, the content of SBR in 100% by mass of the rubber component is preferably 20% by mass or less, more preferably 10% by mass or less, and further preferably 5% by mass or less, and may be 0% by mass. When it is within the above range, the effect tends to be better.

[0050] Both the surface rubber layer composition and the inner rubber layer composition contain a lignin-based material as a filler. In this specification, lignin-based materials refer to lignin and various materials derived from lignin (hereinafter also referred to as lignin derivatives). Among these, the above-mentioned lignin derivatives are preferable from the viewpoint of obtaining a greater effect.

[0051] The nitrogen adsorption specific surface area (N2SA) of the above lignin-based material is 50 μm 2 / g or more is preferable, and 70 μm 2 / g or more is more preferable, and 90 μm 2 / g or more is more preferable, and 110 μm 2 / g or more is particularly preferable. 2 / g or less is preferable, and 250 μm 2 / g or less is more preferable, and 200 μm 2 Within the above range, there is a tendency that the effect is better obtained. The N2SA of the lignin derivative is also preferably in the same range. In this specification, the nitrogen adsorption specific surface area of ​​the lignin-based material is determined according to JIS K6217-2:2001.

[0052] In the tire, the content Lc (parts by mass) of the lignin-based material per 100 parts by mass of the rubber component in the surface rubber layer composition is less than the content Lb (parts by mass) of the lignin-based material per 100 parts by mass of the rubber component in the inner rubber layer composition containing the lignin-based material (Lc <Lb)。 Lc / Lb is preferably 0.8 or less, more preferably 0.6 or less, even more preferably 0.4 or less, and particularly preferably 0.3 or less. The lower limit of Lc / Lb is preferably 0.05 or more, more preferably 0.50 or more, and even more preferably 0.1 or more. Within the above range, the effect tends to be better obtained.

[0053] In the surface rubber layer composition, the content Lc of the lignin-based material is preferably 1 part by mass or more, more preferably 2 parts by mass or more, and even more preferably 3 parts by mass or more, and is preferably 10 parts by mass or less, more preferably 7 parts by mass or less, and even more preferably 5 parts by mass or less, based on 100 parts by mass of the rubber component. When the content is within the above range, the effect tends to be better. The content of the lignin derivative is also preferably in the same range.

[0054] In the inner rubber layer composition, the content Lb of the lignin-based material per 100 parts by mass of the rubber component in the inner rubber layer composition containing the lignin-based material is preferably 3 parts by mass or more, more preferably 5 parts by mass or more, even more preferably 8 parts by mass or more, particularly preferably 10 parts by mass or more, and is preferably 40 parts by mass or less, more preferably 30 parts by mass or less, and even more preferably 20 parts by mass or less, per 100 parts by mass of the rubber component. Within the above ranges, the effect tends to be better obtained. The content of the lignin derivative is also preferably in the same range.

[0055] In the surface rubber layer composition, the content of the lignin-based material in the filler (100% by mass) is preferably 2.0% by mass or more, more preferably 3.0% by mass or more, even more preferably 3.3% by mass or more, particularly preferably 3.6% by mass or more, and is preferably 7.0% by mass or less, more preferably 5.0% by mass or less, and even more preferably 4.5% by mass or less. Within the above ranges, the effect tends to be better obtained. The content of the lignin derivative is also preferably in the same range.

[0056] In the inner rubber layer composition, the lignin-based material content in the filler (100% by mass) of the inner rubber layer composition containing the lignin-based material is preferably 9.0% by mass or more, more preferably 14.0% by mass or more, even more preferably 16.0% by mass or more, particularly preferably 16.6% by mass or more, and is preferably 30.0% by mass or less, more preferably 25.0% by mass or less, and even more preferably 20.0% by mass or less. Within the above ranges, the effect tends to be better obtained. The content of the lignin derivative is also preferably in the same range.

[0057] The lignin derivative is not particularly limited as long as it is a material synthesized from lignin. From the viewpoint of obtaining a greater effect, for example, carbon microparticles obtained from an organic raw material containing lignin as a main component, as described in JP 2009-155199 A, can be preferably used.

[0058] The carbon fine particles can be suitably produced, for example, by the following production methods (1) to (5).

[0059] (1) A method for producing carbon microparticles, in which a solution of an organic raw material containing lignin as a main component is converted into microdroplets, the microdroplets are dried to prepare microparticles, and the microparticles are pyrolyzed at a temperature in the range of 300°C to 1200°C to produce carbon microparticles. (2) A method for producing carbon microparticles, comprising converting a mixed solution of organic raw materials, the main component of which is lignin, and inorganic substances into microdroplets, drying the microdroplets to prepare microparticles, and pyrolyzing the microparticles at a temperature in the range of 300°C to 1200°C to produce carbon microparticles. (3) A method for producing carbon microparticles, comprising forming a mixed solution of an organic raw material containing lignin as a main component and a basic compound into microdroplets, drying the microdroplets to prepare microparticles, and thermally decomposing the microparticles at a temperature in the range of 300°C to 1200°C to increase the specific surface area and produce carbon microparticles. (4) A method for producing carbon microparticles, comprising the steps of: pretreating pulp waste liquor to increase the proportion of lignin in the liquor; forming the pretreated pulp waste liquor into microdroplets; drying the microdroplets to prepare microparticles; and pyrolyzing the microparticles at a temperature in the range of 300°C to 1200°C to produce carbon microparticles. (5) A method for producing carbon microparticles, which comprises pretreating pulp waste liquor to increase the proportion of lignin in the liquor, adding an inorganic substance to the pretreated pulp waste liquor to form a solution, forming the solution into microdroplets, drying the microdroplets to prepare microparticles, and pyrolyzing the microparticles at a temperature in the range of 300°C to 1200°C to produce carbon microparticles.

[0060] In the above-mentioned production method, examples of the organic raw material containing lignin as a main component include lignin, organic matter in waste liquid discharged during the paper pulp production process and waste liquid pretreated therefrom, and pretreated plant raw materials containing lignin such as wood and plants. Lignin is, for example, a polymeric aromatic polymer compound present in wood at 20 to 30% by mass, and is considered to form an intermediate layer between cell membranes, and is also present in the cell membrane. Various methods are known for separating lignin from plants, and these methods can be used. Specific examples of the above-mentioned lignin include alkaline lignin, hydrolyzed lignin, and lignosulfonic acid.

[0061] In the above-mentioned production method, the above-mentioned pretreatment is a treatment for increasing the component ratio of lignin from an organic raw material containing lignin, a treatment for modifying lignin into a structure suitable for producing carbon microparticles, and is a treatment before converting the organic raw material containing lignin into fine droplets. For example, when pulp waste liquid is used as an organic raw material, it is desirable to perform a pretreatment for increasing the component ratio of lignin. Specific examples of the pretreatment include (1) absorbing an acid gas to precipitate and separate lignin, (2) adding an inorganic acid, a polyvalent cation, or an organic amine to precipitate and separate lignin, (3) fermenting and decomposing and removing sugars in the pulp waste liquid, and (4) separating and collecting high molecular weight lignin by ultrafiltration. As the ultrafiltration membrane, for example, a porous membrane with a pore size in the range of 1 to 100 nm can be used.

[0062] In the above-mentioned production method, examples of pretreatment when wood, plants, etc. are used as organic raw materials include known methods such as alkaline decomposition used in pulp production, etc. Furthermore, the proportion of lignin as a component can be increased by using the above-mentioned lignin separation and concentration method, etc., as necessary. Examples of pretreatment include separation and collection of high molecular weight lignin by ultrafiltration, and treatment of precipitating part of the organic components by lowering the hydrogen ion exponent by making the pulp waste liquid absorb carbon dioxide, and separating the organic components from the solution.

[0063] In the above production method, the pyrolysis refers to carbonizing an organic raw material containing lignin by heating it at 300° C. to 1200° C. Generally, pyrolysis is carried out at 500° C. to 800° C.

[0064] In the above-mentioned manufacturing method, examples of the inorganic substance include carbon as a simple substance; water-soluble salts such as metal oxides, hydroxides, carbonates, halides, sulfates, nitrates, silicates, phosphates, and borates; fine particles thereof; and fine fibers thereof. Among them, a metal compound composed of at least one selected from the group consisting of metal oxides, hydroxides, carbonates, and halides is preferable. In this case, the thickness of the carbon wall of the carbon microparticles can be controlled by adjusting the addition ratio of the metal compound based on the property that the thickness of the carbon wall of the carbon microparticles becomes thinner as the addition ratio of the metal compound increases.

[0065] In the above-mentioned production method, the conversion to microdroplets means, for example, converting the pretreated pulp waste liquid into microdroplets having a diameter of about several tens of μm or less by a method such as spraying or ultrasonic atomization.

[0066] In the above-mentioned manufacturing method, it is desirable to contact the carbon fine particles obtained during or after the pyrolysis with a low-reactivity gas before taking them out into the air, thereby reacting the surfaces of the carbon fine particles with the gas to inactivate them and suppress the sudden heat generation when the carbon fine particles are taken out into the air. Here, examples of the low-reactivity gas include water vapor gas and nitrogen gas containing a low concentration of oxygen. Since a gentle reaction with the carbon fine particle surface is required, a completely inert gas such as pure nitrogen does not fall under this category.

[0067] The carbon fine particles obtained by the above-mentioned production method are particles in which lignin in organic matter is pyrolyzed or carbonized. The carbon fine particles have various sizes (diameters of several nm to about 50 μm) and shapes. In addition, the bulk density is, for example, 3 to 300 g / L, and they are lightweight.

[0068] Hollow carbon particles can also be produced by the above-mentioned production method. The hollow carbon fine particles have, for example, an outer diameter of 0.2 to 50 μm and a carbon wall thickness of 0.05 to 20 μm.

[0069] In the hollow carbon fine particles, for example, the mass ratio of the lignin to the basic compound is 1:0.5 to 1:2. In the hollow carbon microparticles, the mass ratio of the lignin to the metal compound is, for example, 1:3 to 1:20.

[0070] For example, a solution of lignin and metasilicate is turned into microdroplets, the microdroplets are dried to prepare microparticles, and the microparticles are pyrolyzed at a temperature in the range of 300°C to 1200°C to produce hollow carbon microparticles having an outer diameter of 0.2 to 50 μm and a carbon wall thickness of 0.05 to 20 μm, or hollow carbon microparticles whose carbon walls are composed of carbon nanopipes having an outer diameter of 5 to 50 nm and a carbon wall thickness of 1 to 5 nm. Here, the mass ratio of the lignin to the metasilicate is, for example, 1:3 to 1:20.

[0071] In addition, a solution of lignin and orthosilicate is converted into microdroplets, which are then dried to prepare microparticles. The microparticles are then thermally decomposed at a temperature in the range of 300°C to 1200°C to produce nanoparticles with an outer diameter of 3 to 30 nm, a carbon wall thickness of 1 to 5 nm, and a specific surface area of ​​1400 to 1600 m. 2 It is possible to produce hollow, non-graphitic carbon particles with a particle size of 0.01 g / g. Here, the mass ratio between the lignin and the orthosilicate is, for example, 1:5 to 1:20.

[0072] More specifically, for example, an aqueous solution of lignosulfonic acid with a total concentration of 5% is spray-dried to prepare lignosulfonic acid microparticles, which are then heat-treated at 600°C for 1 hour in a nitrogen atmosphere and allowed to cool, thereby producing hollow carbon microparticles with a diameter of several μm to approximately 10 μm.

[0073] Alternatively, hollow carbon microparticles can be produced by spray-drying an aqueous solution of lignin and sodium hydroxide (mass ratio 1:0.25) with a total concentration of 5%, preparing composite microparticles, which are then heat-treated at 600°C for 1 hour in a nitrogen atmosphere, allowed to cool, washed with water, and further dried. Hollow carbon microparticles can also be produced by carrying out the same treatment on an aqueous solution of lignin and sodium hydroxide with a total concentration of 5%, with a mass ratio of lignin and sodium hydroxide of 1:0.5. Hollow carbon microparticles can also be produced by carrying out the same treatment on an aqueous solution of lignin and sodium hydroxide with a total concentration of 5%, with a mass ratio of lignin and sodium hydroxide of 1:1.

[0074] As the lignin derivative, from the viewpoint of obtaining a greater effect, for example, lignin treated by hydrothermal carbonization as described in Japanese Patent No. 6704475 can also be suitably used.

[0075] The lignin treated by hydrothermal carbonization can be produced from a lignin-containing material. Examples of the lignin-containing material include plant lignin (coniferous wood (gymnosperms) lignin, broadleaf wood (angiosperms) lignin, annual plant (herbaceous plant) lignin, etc.).

[0076] The hydrothermal carbonization of lignin (treatment by hydrothermal carbonization) can destroy the polymer structure of lignin. The hydrothermal carbonization includes, for example, a step of obtaining a lignin-containing material and a step of treating the lignin-containing material in an aqueous suspension under high temperature and high pressure conditions. Therefore, in the hydrothermal carbonization, the lignin-containing material is partially decomposed by heat in a liquid state. The hydrothermal carbonization also converts the lignin-containing material into a lignin derivative of substantially uniform quality, and the lignin derivative contains functional groups.

[0077] The hydrothermal carbonization treatment can also be used to at least partially purify the lignin-containing material. Generally, the lignin is at least partially carbonized. During the hydrothermal carbonization treatment, the lignin is surrounded by water. The degree of decomposition of the lignin by the hydrothermal carbonization treatment can be adjusted by appropriately selecting the temperature, pressure, pH of the water suspension, etc. The reaction conditions for the hydrothermal carbonization of the lignin can be appropriately selected, thereby producing a lignin derivative having predetermined properties. The reaction conditions include pH, pressure, maximum temperature of the input material, and residence time.

[0078] The hydrothermal carbonization treatment can be carried out in a reactor. For example, a batch reactor can be used as the reactor. The hydrothermal carbonization treatment of lignin can be carried out by controlling the internal pressure of the reactor so that the water in the reactor is maintained in a liquid state during the hydrothermal carbonization. The internal pressure of the reactor during the hydrothermal carbonization reaction is, for example, 10 to 40 bar, preferably 15 to 40 bar. In the hydrothermal carbonization treatment, it is desirable to control the temperature of the aqueous suspension containing lignin so that the lignin begins to disintegrate into small fragments. The temperature of the hydrothermal carbonization reaction is preferably 150°C or higher, and preferably 300°C or lower, more preferably 250°C or lower. The temperature of the hydrothermal carbonization reaction refers to the temperature of the aqueous suspension in the reactor during the hydrothermal carbonization reaction.

[0079] In the hydrothermal carbonization treatment, it is desirable to control the pH of the aqueous suspension containing lignin, and lignin is highly soluble under alkaline conditions. In the hydrothermal carbonization treatment, the pH of the suspension containing lignin affects the particle size of the lignin derivative formed, and the pH of the suspension containing lignin is preferably adjusted to a value exceeding 7, more preferably exceeding 8. The pH of the aqueous suspension containing lignin can be adjusted before the hydrothermal carbonization treatment. In an alkaline suspension, polymerization of lignin is generally suppressed at a pH of 10 or more. The particle size of the lignin derivative formed is affected by the pH of the hydrothermal carbonization treatment. In the hydrothermal carbonization treatment, it is desirable to reduce the hydrogen ion concentration of the aqueous suspension containing lignin before the hydrothermal carbonization treatment, thereby reducing the particle size of the lignin derivative formed. In the hydrothermal carbonization treatment, it is desirable to increase the hydrogen ion concentration of the aqueous suspension containing lignin before the hydrothermal carbonization treatment, thereby increasing the particle size of the lignin derivative formed. The particle size of the lignin derivative refers to the average particle size after hydrothermal carbonization treatment.

[0080] By the above-mentioned hydrothermal carbonization treatment, a lignin derivative having a functional group can be prepared, and the functional group can include a hydroxyl group, a carboxyl group, a methoxy group, a phenolic hydroxyl group, and the like.

[0081] The hydrothermal carbonization treatment can concentrate the carbon content of lignin. The concentration of the carbon content of lignin occurs due to dehydration, decarboxylation, etc. At low temperatures, dehydration predominates, and at high temperatures, decarboxylation predominates. At higher temperatures, both the dehydration and decarboxylation reactions proceed more rapidly, so it is desirable to set the reaction temperature of the hydrothermal carbonization treatment of lignin to a high temperature.

[0082] The hydrothermal carbonization treatment can preserve, at least to some extent, the surface active functional groups of the input lignin derivative, so that the lignin derivative produced contains functional groups that can be combined with other compounds through chemical reactions, providing a material with a relatively large amount of functional groups, which is generally much higher than that of, for example, carbon black.

[0083] The surface rubber layer composition and the inner rubber layer composition may contain a filler other than the lignin-based material. Such fillers are not particularly limited, and materials known in the rubber field can be used, for example, inorganic fillers such as carbon black, silica, calcium carbonate, talc, alumina, clay, aluminum hydroxide, aluminum oxide, mica, biochar, poorly dispersible fillers, etc. Among them, carbon-derived fillers (carbon-containing fillers) such as carbon black, and silica are preferred. The fillers may be used alone or in combination of two or more. In particular, from the viewpoint of obtaining a better effect, the surface rubber layer composition preferably contains at least one of carbon black and silica, and more preferably contains carbon black and silica. From the viewpoint of obtaining a better effect, the composition for the inner rubber layer preferably contains at least one of carbon black and silica, more preferably contains carbon black, and further preferably contains carbon black and silica.

[0084] In the above-mentioned surface rubber layer composition and the above-mentioned inner rubber layer composition, usable carbon black is not particularly limited, and examples thereof include N134, N110, N220, N234, N219, N339, N330, N326, N351, N550, and N762. The raw material of carbon black may be a biomass material such as lignin or vegetable oil, or may be pyrolysis oil obtained by pyrolyzing waste tires. The carbon black may be produced by combustion such as a furnace method, hydrothermal carbonization (HTC), or pyrolysis of methane such as a thermal black method. As commercially available products, products from Asahi Carbon Co., Ltd., Cabot Japan Co., Ltd., Tokai Carbon Co., Ltd., Mitsubishi Chemical Corporation, Lion Corporation, Nippon Steel Carbon Co., Ltd., Columbia Carbon Co., Ltd., and the like may be used. Carbon black may be used alone or in combination of two or more kinds.

[0085] The nitrogen adsorption specific surface area (N2SA) of carbon black is 50m 2 / g or more is preferable, and 80m 2 / g or more is more preferable, and 100m 2 / g or more is more preferable. 2 / g or less is preferable, and 130m 2 / g or less is more preferable, and 120m 2 Within the above range, there is a tendency that the effect is better obtained. The nitrogen adsorption specific surface area of ​​carbon black can be determined in accordance with JIS K6217-2:2001.

[0086] The dibutyl phthalate oil absorption (DBP) of the carbon black is preferably 40 ml / 100 g or more, more preferably 60 ml / 100 g or more, and even more preferably 70 ml / 100 g or more. The DBP is preferably 200 ml / 100 g or less, more preferably 150 ml / 100 g or less, and even more preferably 100 ml / 100 g or less. Within the above range, the effect tends to be better. The DBP of carbon black is determined by the measurement method of JIS K6217-4:2001.

[0087] In the above-mentioned surface rubber layer composition, the content of carbon black is preferably 5 parts by mass or more, more preferably 8 parts by mass or more, even more preferably 10 parts by mass or more, and is preferably 80 parts by mass or less, more preferably 60 parts by mass or less, even more preferably 40 parts by mass or less, and particularly preferably 20 parts by mass or less, based on 100 parts by mass of the rubber component. Within the above ranges, the effect tends to be better obtained.

[0088] In the inner rubber layer composition, the content of carbon black in the inner rubber layer composition containing the lignin-based material is, relative to 100 parts by mass of the rubber component, preferably 10 parts by mass or more, more preferably 15 parts by mass or more, even more preferably 20 parts by mass or more, and is preferably 70 parts by mass or less, more preferably 50 parts by mass or less, even more preferably 40 parts by mass or less, and particularly preferably 30 parts by mass or less. Within the above ranges, the effect tends to be better obtained. The carbon black content in the inner rubber layer that does not contain a lignin-based material is also desirably in the same range.

[0089] In the above-mentioned surface rubber layer composition and the above-mentioned inner rubber layer composition, the silica that can be used is not particularly limited, and for example, silica prepared by a dry method (anhydrous silica), silica prepared by a wet method (hydrated silica), and other silicas that are common in the tire industry can be used. The raw material of the silica is not particularly limited, and for example, it may be a mineral-derived raw material such as quartz, a biological raw material such as rice husk (for example, silica made from a biomass material such as rice husk), or silica recycled from a product containing silica may be used. Among them, hydrated silica prepared by a wet method is preferred because it contains a large number of silanol groups. These silicas may be used alone or in combination of two or more types.

[0090] Silica made from biomass materials can be obtained, for example, by extracting silicate from rice husk ash obtained by burning rice husks using a sodium hydroxide solution, and then reacting the silicate with sulfuric acid in the same manner as conventional wet-process silica to produce a silicon dioxide precipitate, which is then filtered, washed with water, dried, and pulverized.

[0091] The silica recycled from a product containing silica can be, for example, silica recovered from a product containing silica, such as electronic parts such as semiconductors, tires, desiccants, and filtering materials such as diatomaceous earth. The recovery method is not particularly limited, and examples include pyrolysis and decomposition by electromagnetic waves. Among them, silica recovered from electronic parts such as semiconductors or tires is preferred.

[0092] When silica crystallizes, it does not dissolve in water and its component silicic acid cannot be used. By controlling the combustion temperature and combustion time, it is possible to suppress the crystallization of silica in rice husk ash (see JP 2009-2594 A, Akita Prefectural University Web Journal B / 2019, vol. 6, p. 216-222, etc.).

[0093] As the amorphous silica extracted from rice husks, commercially available products such as those sold by Wilmar Co. can be used.

[0094] The nitrogen adsorption specific surface area (N2SA) of the silica is preferably 50 m 2 / g or more, more preferably 100m 2 / g or more, more preferably 150m 2 The upper limit of the N2SA of silica is not particularly limited, but is preferably 350 m 2 / g or less, more preferably 300m 2 / g or less, more preferably 250m 2 Within the above range, there is a tendency for the effect to be better obtained. The N2SA of silica is a value measured by the BET method in accordance with ASTM D3037-93.

[0095] In the surface rubber layer composition, the silica content Sc relative to 100 parts by mass of the rubber component is preferably 20 parts by mass or more, more preferably 30 parts by mass or more, even more preferably 50 parts by mass or more, particularly preferably 70 parts by mass or more, and is preferably 150 parts by mass or less, more preferably 100 parts by mass or less, and even more preferably 90 parts by mass or less. Within the above ranges, the effect tends to be better obtained. The content of the plant-derived silica and the content of the rice husk silica are also desirably in the same range.

[0096] When the surface rubber layer composition contains a certain amount of silica or more, particularly 30 parts by mass or more, the mechanism by which the effect is improved is not clear, but since the silica surface also contains OH groups, it is thought that a network is formed with the lignin-based material, which increases the rigidity and makes it easier to obtain the effect. Therefore, it is presumed that the steering stability on dry road surfaces is significantly improved.

[0097] In the inner rubber layer composition, the silica content Sb per 100 parts by mass of the rubber component in the inner rubber layer composition containing the lignin-based material is preferably 5 parts by mass or more, more preferably 20 parts by mass or more, even more preferably 30 parts by mass or more, and is preferably 100 parts by mass or less, more preferably 70 parts by mass or less, even more preferably 50 parts by mass or less. Within the above ranges, the effect tends to be better obtained. The content of the plant-derived silica and the content of the rice husk silica are also desirably in the same range. The silica content of the inner rubber layer that does not contain a lignin-based material is also desirably in a similar range.

[0098] Examples of the poorly dispersible filler that can be used in the surface rubber layer composition and the inner rubber layer composition include microfibrillated plant fibers, short fiber cellulose, gel compounds, etc. Among these, microfibrillated plant fibers are preferred.

[0099] The microfibrillated plant fiber is preferably cellulose microfibril, since it has good reinforcing properties. The cellulose microfibril is not particularly limited as long as it is derived from a natural product, and examples thereof include those derived from resource biomass such as fruits, grains, and root vegetables, wood, bamboo, hemp, jute, and kenaf, and pulp, paper, cloth, agricultural waste, waste biomass such as food waste and sewage sludge obtained from these as raw materials, unused biomass such as rice straw, wheat straw, and thinned wood, as well as cellulose produced by sea squirts, acetic acid bacteria, etc. These microfibrillated plant fibers may be used alone or in combination of two or more.

[0100] In this specification, cellulose microfibrils typically refer to cellulose fibers having an average fiber diameter of 10 μm or less, more typically cellulose fibers having a microstructure formed by the aggregation of cellulose molecules and an average fiber diameter of 500 nm or less. Typical cellulose microfibrils are formed, for example, as an aggregate of cellulose fibers having the above-mentioned average fiber diameter.

[0101] When the surface rubber layer composition and the inner rubber layer composition contain a poorly dispersible filler, the content of the poorly dispersible filler is preferably 1 part by mass or more, more preferably 3 parts by mass or more, and even more preferably 5 parts by mass or more, based on 100 parts by mass of the rubber component. The upper limit of the content is preferably 50 parts by mass or less, more preferably 30 parts by mass or less, even more preferably 20 parts by mass or less, and particularly preferably 10 parts by mass or less. Within the above range, the effect tends to be better obtained.

[0102] In the surface rubber layer composition, the content of the filler (total amount of fillers such as lignin-based materials, carbon black, silica, etc.) is preferably 60 parts by mass or more, more preferably 85 parts by mass or more, even more preferably 95 parts by mass or more, particularly preferably 100 parts by mass or more, and is preferably 150 parts by mass or less, more preferably 140 parts by mass or less, and even more preferably 120 parts by mass or less, per 100 parts by mass of the rubber component. Within the above ranges, the effect tends to be better obtained.

[0103] In the inner rubber layer composition, the content of the filler in the inner rubber layer composition containing the lignin-based material (total amount of fillers such as the lignin-based material, carbon black, and silica) is preferably 30 parts by mass or more, more preferably 40 parts by mass or more, even more preferably 50 parts by mass or more, and particularly preferably 53 parts by mass or more, per 100 parts by mass of the rubber component, and is preferably 120 parts by mass or less, more preferably 90 parts by mass or less, and even more preferably 70 parts by mass or less. Within the above ranges, the effect tends to be better obtained. The content of the filler in the inner rubber layer that does not contain a lignin-based material is also desirably in the same range.

[0104] The surface rubber layer composition and the inner rubber layer composition preferably further contain a silane coupling agent. The silane coupling agent is not particularly limited, and those known in the rubber field can be used. For example, bis(3-triethoxysilylpropyl)tetrasulfide, bis(2-triethoxysilylethyl)tetrasulfide, bis(4-triethoxysilylbutyl)tetrasulfide, bis(3-trimethoxysilylpropyl)tetrasulfide, bis(2-trimethoxysilylethyl)tetrasulfide, bis(2-triethoxysilylethyl)trisulfide, bis(4-trimethoxysilylbutyl)trisulfide, bis(3-triethoxysilylpropyl)disulfide, bis(2-triethoxysilylethyl)disulfide, bis(4-triethoxysilylbutyl)disulfide, bis(3-trimethoxysilylpropyl)disulfide, bis(2-trimethoxysilylethyl)disulfide, bis(4-trimethoxysilylbutyl)disulfide, bis(3-trimethoxysilylpropyl)disulfide, bis(2-trimethoxysilylethyl)disulfide, bis(4-trimethoxysilylbutyl)disulfide, 3-trimethoxysilylpropyl-N, Examples of such silylsilanes include sulfide-based silylsilanes such as N-dimethylthiocarbamoyl tetrasulfide, 2-triethoxysilylethyl-N,N-dimethylthiocarbamoyl tetrasulfide, and 3-triethoxysilylpropyl methacrylate monosulfide; mercapto-based silylsilanes such as 3-mercaptopropyltrimethoxysilane, 2-mercaptoethyltriethoxysilane, and Momentive's NXT and NXT-Z; vinyl-based silylsilanes such as vinyltriethoxysilane and vinyltrimethoxysilane; amino-based silylsilanes such as 3-aminopropyltriethoxysilane and 3-aminopropyltrimethoxysilane; glycidoxy-based silylsilanes such as γ-glycidoxypropyltriethoxysilane and γ-glycidoxypropyltrimethoxysilane; nitro-based silylsilanes such as 3-nitropropyltrimethoxysilane and 3-nitropropyltriethoxysilane; and chloro-based silylsilanes such as 3-chloropropyltrimethoxysilane and 3-chloropropyltriethoxysilane. Commercially available products include those manufactured by Degussa, Momentive, Shin-Etsu Silicones, Tokyo Chemical Industry, Azumax, and Dow Corning Toray Co., Ltd. These may be used alone or in combination of two or more.

[0105] In the above surface rubber layer composition and the above inner rubber layer composition, the content of the silane coupling agent is preferably 0.1 parts by mass or more, more preferably 3 parts by mass or more, even more preferably 5 parts by mass or more, and particularly preferably 7 parts by mass or more, based on 100 parts by mass of silica. The upper limit of the content is preferably 50 parts by mass or less, more preferably 20 parts by mass or less, even more preferably 15 parts by mass or less, and particularly preferably 10 parts by mass or less. Within the above range, the effect tends to be better obtained.

[0106] The surface rubber layer composition and the inner rubber layer composition may contain a plasticizer. In this specification, a plasticizer is a material that imparts plasticity to a rubber component, and is a concept that includes both plasticizers that are liquid (liquid state) at room temperature (25°C) and plasticizers that are solid at room temperature (25°C). Examples of plasticizers include resin components, oils, liquid polymers, ester-based plasticizers, and the like. These plasticizers may be derived from petroleum, may be derived from biomass, or may be derived from naphtha recycled from rubber products or non-rubber products. In addition, low molecular weight hydrocarbon components obtained by pyrolysis and extraction of used tires or products containing various components may be used as plasticizers. These plasticizers may be used alone or in combination of two or more types.

[0107] Examples of the plasticizer include oil, liquid polymer, resin, etc. These may be used alone or in combination of two or more kinds.

[0108] Examples of the oil include process oil, vegetable oil, and animal oil. Examples of the process oil include paraffin-based process oil (mineral oil), naphthenic process oil, and aromatic process oil. Specific examples of the process oil include MES (Mild Extract Solvated), DAE (Distillate Aromatic Extract), TDAE (Treated Distillate Aromatic Extract), TRAE (Treated Residual Aromatic Extract), and RAE (Residual Aromatic Extract). In addition, as an environmental measure, process oil with a low content of polycyclic aromatic compound (PCA) compounds can be used. Examples of the low PCA content process oil include MES, TDAE, and heavy naphthenic oil. In addition, from the viewpoint of life cycle assessment, waste oil after use in rubber mixers and engines, and refined waste edible oil used in cooking restaurants may be used.

[0109] In this specification, examples of vegetable oils include linseed oil, rapeseed oil, safflower oil, soybean oil, corn oil, cottonseed oil, rice oil, tall oil, sesame oil, perilla oil, castor oil, paulownia oil, pine oil, pine tar oil, sunflower oil, coconut oil, palm oil, palm kernel oil, olive oil, camellia oil, jojoba oil, macadamia nut oil, peanut oil, grapeseed oil, and wood wax. In addition, examples of vegetable oils include refined oils (such as salad oils) obtained by refining the above-mentioned oils, transesterified oils obtained by transesterifying the above-mentioned oils, hardened oils obtained by hydrogenating the above-mentioned oils, thermally polymerized oils obtained by thermally polymerizing the above-mentioned oils, oxidatively polymerized oils obtained by oxidizing the above-mentioned oils, and waste edible oils obtained by recovering oils that have been used as edible oils or the like. The vegetable oils may be liquid or solid at room temperature (25° C.). These vegetable oils may be used alone or in combination of two or more.

[0110] The vegetable oil according to the present embodiment preferably contains acylglycerol, and more preferably contains triacylglycerol. In this specification, acylglycerol refers to a compound in which a hydroxyl group of glycerin and a fatty acid are ester-bonded. The acylglycerol is not particularly limited, and may be 1-monoacylglycerol, 2-monoacylglycerol, 1,2-diacylglycerol, 1,3-diacylglycerol, or triacylglycerol. Furthermore, the acylglycerol may be a monomer, a dimer, or a polymer of trimer or more. Incidentally, dimer or more acylglycerols can be obtained by thermal polymerization, oxidative polymerization, or the like. Moreover, the acylglycerol may be liquid or solid at room temperature (25°C).

[0111] The method for confirming whether the rubber composition contains the acylglycerol is not particularly limited, but may be any of the following methods: 1 For example, a rubber composition containing triacylglycerol is immersed in deuterated chloroform at room temperature (25°C) for 24 hours, and after removing the rubber composition, 1 When H-NMR was measured, signals were observed at around 5.26 ppm, around 4.28 ppm, and around 4.15 ppm when the signal of tetramethylsilane (TMS) was set at 0.00 ppm, and the signals were presumed to be signals derived from hydrogen atoms bonded to carbon atoms adjacent to oxygen atoms of ester groups. Note that "around" in this paragraph refers to a range of ±0.10 ppm.

[0112] The fatty acid is not particularly limited, and may be an unsaturated fatty acid or a saturated fatty acid. Examples of the unsaturated fatty acid include monounsaturated fatty acids such as oleic acid, and polyunsaturated fatty acids such as linoleic acid and linolenic acid. Examples of the saturated fatty acid include butyric acid and lauric acid.

[0113] Among them, the fatty acid is preferably a fatty acid with few double bonds, i.e., a saturated fatty acid or a monounsaturated fatty acid, and oleic acid is preferable. As the vegetable oil containing such a fatty acid, for example, a vegetable oil containing a saturated fatty acid or a monounsaturated fatty acid may be used, or a vegetable oil modified by ester exchange or the like may be used. In addition, in order to produce a vegetable oil containing such a fatty acid, a plant may be improved by breeding, genetic recombination, genome editing, or the like.

[0114] As the oil, for example, oils commercially available from Idemitsu Kosan Co., Ltd., Sankyo Yuka Kogyo Co., Ltd., ENEOS Corporation, Orisoi Co., Ltd., H&R Corporation, Toyokuni Oil Mills Co., Ltd., Fuji Kosan Co., Ltd., Nisshin Oillio Group Co., Ltd., etc. can be used.

[0115] Examples of the liquid polymer include liquid diene polymers (liquid rubber) and liquid farnesene polymers at 25°C. Examples of liquid rubber include liquid styrene butadiene copolymers (liquid SBR), liquid butadiene polymers (liquid BR), liquid isoprene polymers (liquid IR), liquid styrene isoprene copolymers (liquid SIR), liquid styrene butadiene styrene block copolymers (liquid SBS block polymers), and liquid styrene isoprene styrene block copolymers (liquid SIS block polymers). The ends or main chains of these may be modified with polar groups. Hydrogenated products of these may also be used.

[0116] The liquid diene polymer has a weight average molecular weight (Mw) of 1.0×10 in terms of polystyrene measured by gel permeation chromatography (GPC). 3 ~5.0×10 4 Preferably, it is 3.0×10 3 ~1.5×10 4 The lower or upper limit of Mw of the liquid diene polymer may be 4,500 or 8,500. In this specification, the Mw of the liquid diene-based polymer is a polystyrene-equivalent value measured by gel permeation chromatography (GPC).

[0117] As the liquid diene polymer, for example, products available from Sartomer Co., Ltd., Kuraray Co., Ltd., etc. can be used.

[0118] The resin may be a resin that is commonly used as a tire compound, and may be liquid or solid at room temperature (25°C). Examples of the resin include aromatic vinyl polymers, coumarone-indene resins, coumarone resins, indene resins, phenolic resins, rosin resins, petroleum resins, terpene resins, and acrylic resins. The resin may also be a hydrogenated resin (hydrogenated resin). These may be used alone or in combination of two or more. The resin itself may also be a copolymer of monomer components of multiple origins. Among these, aromatic vinyl polymers, petroleum resins, terpene resins, and hydrogenated resins thereof are preferable.

[0119] When a resin that is solid at room temperature is used, the softening point of the resin is preferably 50° C. or higher, more preferably 55° C. or higher, even more preferably 60° C. or higher, and particularly preferably 85° C. or higher. Also, the softening point is preferably 160° C. or lower, more preferably 150° C. or lower, even more preferably 140° C. or lower, and particularly preferably 100° C. or lower. Within the above range, the effect tends to be better obtained. When the resin is liquid at room temperature, the softening point is preferably 20° C. or lower, more preferably 10° C. or lower, and even more preferably 0° C. or lower. In the case of hydrogenated resins, it is desirable for the softening point to be similar to that mentioned above. The softening point of the resin is the temperature at which the ball drops when the softening point specified in JIS K6220-1:2001 is measured using a ring and ball softening point tester.

[0120] The aromatic vinyl polymer is a polymer containing an aromatic vinyl monomer as a structural unit. For example, it can be a resin obtained by polymerizing α-methylstyrene and / or styrene, and specifically, it can be a homopolymer of styrene (styrene resin), a homopolymer of α-methylstyrene (α-methylstyrene resin), a copolymer of α-methylstyrene and styrene, a copolymer of styrene and another monomer, etc.

[0121] The coumarone-indene resin is a resin containing coumarone and indene as main monomer components constituting the resin skeleton (main chain). Other monomer components contained in the skeleton besides coumarone and indene include styrene, α-methylstyrene, methylindene, vinyltoluene, etc.

[0122] The coumarone resin is a resin containing coumarone as a main monomer component constituting the skeleton (main chain) of the resin.

[0123] The indene resin is a resin containing indene as a main monomer component constituting the skeleton (main chain) of the resin.

[0124] The phenolic resin may be a known polymer obtained by reacting phenol with an aldehyde such as formaldehyde, acetaldehyde, or furfural in the presence of an acid or alkali catalyst. Among these, those obtained by reacting with an acid catalyst (such as novolac-type phenolic resin) are preferred.

[0125] Examples of the rosin resin include rosin-based resins such as natural rosin, polymerized rosin, modified rosin, ester compounds thereof, and hydrogenated products thereof.

[0126] Examples of the petroleum resin include C5 resin, C9 resin, C5 / C9 resin, dicyclopentadiene (DCPD) resin, C9 / DCPD resin, and hydrogenated versions of these resins. Among these, DCPD resin, hydrogenated DCPD resin, C9 / DCPD resin, and C9 / hydrogenated DCPD resin are preferred.

[0127] The terpene resin is a polymer containing terpene as a constituent unit. For example, polyterpene resin obtained by polymerizing a terpene compound, aromatic modified terpene resin obtained by polymerizing a terpene compound and an aromatic compound, etc. can be mentioned. As the aromatic modified terpene resin, terpene phenol resin made from terpene compounds and phenolic compounds, terpene styrene resin made from terpene compounds and styrene compounds, and terpene phenol styrene resin made from terpene compounds, phenolic compounds, and styrene compounds can also be used. In addition, examples of the terpene compound include α-pinene, β-pinene, etc., examples of the phenolic compound include phenol, bisphenol A, etc., and examples of the aromatic compound include styrene compounds (styrene, α-methylstyrene, etc.). Among them, aromatic modified terpene resin is preferable.

[0128] The acrylic resin is a polymer containing an acrylic monomer as a constituent unit. For example, a styrene-acrylic resin having a carboxyl group and obtained by copolymerizing an aromatic vinyl monomer component and an acrylic monomer component, such as a styrene-acrylic resin, can be used. Among them, a solventless carboxyl group-containing styrene-acrylic resin can be preferably used.

[0129] Examples of the resins that can be used include products from Maruzen Petrochemical Co., Ltd., Sumitomo Bakelite Co., Ltd., Yasuhara Chemical Co., Ltd., Tosoh Corporation, Rutgers Chemicals, BASF, Arizona Chemical Company, Exxon Mobil Corporation, KRATON, Nippon Paint Chemical Co., Ltd., Nippon Shokubai Co., Ltd., ENEOS Corporation, Arakawa Chemical Industries, Ltd., and Taoka Chemical Co., Ltd.

[0130] From the viewpoint of sustainability, it is desirable to use, as the plasticizer, a plant-derived plasticizer such as the plant-derived oil or farnesene-based polymer.

[0131] Farnesene polymers are polymers obtained by polymerizing farnesene and have structural units based on farnesene. Farnesene has isomers such as α-farnesene ((3E,7E)-3,7,11-trimethyl-1,3,6,10-dodecatetraene) and β-farnesene (7,11-dimethyl-3-methylene-1,6,10-dodecatriene), but (E)-β-farnesene, which has the following structure, is preferred. [ka]

[0132] The farnesene-based polymer may be a homopolymer of farnesene (farnesene homopolymer) or a copolymer of farnesene and a vinyl monomer (farnesene-vinyl monomer copolymer). These may be used alone or in combination of two or more. Among them, a copolymer of farnesene and a vinyl monomer is preferred.

[0133] Examples of vinyl monomers include aromatic vinyl compounds such as styrene, 2-methylstyrene, 3-methylstyrene, 4-methylstyrene, α-methylstyrene, 2,4-dimethylstyrene, 2,4-diisopropylstyrene, 4-tert-butylstyrene, 5-t-butyl-2-methylstyrene, vinylethylbenzene, divinylbenzene, trivinylbenzene, divinylnaphthalene, tert-butoxystyrene, vinylbenzyldimethylamine, (4-vinylbenzyl)dimethylaminoethylether, N,N-dimethylaminoethylstyrene, N,N-dimethylaminomethylstyrene, 2-ethylstyrene, 3-ethylstyrene, 4-ethylstyrene, 2-t-butylstyrene, 3-t-butylstyrene, 4-t-butylstyrene, vinylxylene, vinylnaphthalene, vinyltoluene, vinylpyridine, diphenylethylene, and tertiary amino group-containing diphenylethylene, as well as conjugated diene compounds such as butadiene and isoprene. These may be used alone or in combination of two or more. Among these, butadiene is preferred. That is, the farnesene-vinyl monomer copolymer is preferably a copolymer of farnesene and butadiene (farnesene-butadiene copolymer).

[0134] In the farnesene-vinyl monomer copolymer, the copolymerization ratio by mass of farnesene and vinyl monomer (farnesene / vinyl monomer) is preferably 40 / 60 to 90 / 10.

[0135] The farnesene-based polymer preferably has a weight average molecular weight (Mw) of 3000 or more and 300,000 or less. The Mw of the farnesene-based polymer is preferably 8000 or more, more preferably 10,000 or more, and is preferably 100,000 or less, more preferably 60,000 or less, and even more preferably 50,000 or less. Within the above ranges, the effect tends to be more preferably obtained.

[0136] The farnesene-based polymer may be either a liquid or solid polymer at room temperature (25° C.), and is preferably a liquid farnesene-based polymer that is a liquid at room temperature (25° C.).

[0137] In the above-mentioned surface rubber layer composition, the content of the plasticizer (total amount of the plasticizer) is preferably 18 parts by mass or more, more preferably 25 parts by mass or more, even more preferably 30 parts by mass or more, and particularly preferably 36 parts by mass or more, per 100 parts by mass of the rubber component. The upper limit is preferably 60 parts by mass or less, more preferably 50 parts by mass or less, and even more preferably 45 parts by mass or less. Within the above range, the effect tends to be better obtained. The plasticizer content includes the amount of oil and resin contained in the oil-extended rubber and resin-extended rubber.

[0138] In the above-mentioned surface rubber layer composition, the content of the solid plasticizer in a solid state at room temperature (25°C) is preferably 8 parts by mass or more, more preferably 13 parts by mass or more, and even more preferably 16 parts by mass or more, based on 100 parts by mass of the rubber component. The upper limit is preferably 40 parts by mass or less, more preferably 30 parts by mass or less, and even more preferably 25 parts by mass or less. Within the above range, the effect tends to be better obtained. The content of the resin in a solid state at room temperature (25° C.) and the content of the aromatic vinyl polymer are also desirably in the same range.

[0139] In the above-mentioned surface rubber layer composition, the content of the liquid plasticizer in a liquid state at room temperature (25°C) is preferably 10 parts by mass or more, more preferably 15 parts by mass or more, and even more preferably 20 parts by mass or more, based on 100 parts by mass of the rubber component. The upper limit is preferably 50 parts by mass or less, more preferably 40 parts by mass or less, and even more preferably 30 parts by mass or less. Within the above range, the effect tends to be better obtained. The liquid plasticizer content includes the amount of oil contained in the oil-extended rubber and the amount of liquid resin in the resin-extended rubber that has been extended with the liquid resin. A similar range is also desirable for the oil content that is liquid at room temperature (25°C).

[0140] In the inner rubber layer composition, the content of the plasticizer (total amount of plasticizer) in the inner rubber layer composition containing the lignin-based material is preferably 30 parts by mass or less, more preferably 10 parts by mass or less, and even more preferably 5 parts by mass or less, per 100 parts by mass of the rubber component, and may be 0 parts by mass. When the content is within the above range, the effect tends to be better. The plasticizer content includes the amount of oil and resin contained in the oil-extended rubber and resin-extended rubber. The plasticizer content of the inner rubber layer that does not contain a lignin-based material is also desirably in a similar range.

[0141] In the inner rubber layer composition, the content of the solid plasticizer in a solid state at room temperature (25° C.) in the inner rubber layer composition containing the lignin-based material is preferably 30 parts by mass or less, more preferably 10 parts by mass or less, and even more preferably 5 parts by mass or less, per 100 parts by mass of the rubber component, and may be 0 parts by mass. When the content is within the above range, the effect tends to be better. Within the above range, better effects tend to be obtained. The content of the above resin in a solid state at room temperature (25° C.) is also desirably in the same range. The content of the solid plasticizer in a solid state at room temperature (25° C.) in the inner rubber layer that does not contain a lignin-based material is also desirably in the same range.

[0142] In the inner rubber layer composition, the content of the liquid plasticizer in a liquid state at room temperature (25° C.) in the inner rubber layer composition containing the lignin-based material is preferably 30 parts by mass or less, more preferably 10 parts by mass or less, and even more preferably 5 parts by mass or less, per 100 parts by mass of the rubber component, and may be 0 parts by mass. When the content is within the above range, the effect tends to be better. Within the above range, better effects tend to be obtained. The liquid plasticizer content includes the amount of oil contained in the oil-extended rubber and the amount of liquid resin in the resin-extended rubber that has been extended with the liquid resin. A similar range is also desirable for the oil content that is liquid at room temperature (25°C). The content of the liquid plasticizer in a liquid state at room temperature (25° C.) in the inner rubber layer that does not contain a lignin-based material is also desirably in the same range.

[0143] From the viewpoints of crack resistance, ozone resistance, and the like, the surface rubber layer composition and the inner rubber layer composition preferably contain an antioxidant.

[0144] The antioxidant is not particularly limited, and examples thereof include naphthylamine-based antioxidants such as phenyl-α-naphthylamine; diphenylamine-based antioxidants such as octylated diphenylamine and 4,4'-bis(α,α'-dimethylbenzyl)diphenylamine; N-isopropyl-N'-phenyl-p-phenylenediamine, N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine (6PPD), N,N'-bis(1,4-dimethylpentyl)-p-phenylenediamine (77PD), N,N'-diphenyl-p-phenylenediamine (DPPD), N,N'-ditolyl-p-phenylenediamine, and the like. p-phenylenediamine-based antioxidants such as N-isopropyl-N'-phenyl-p-phenylenediamine (DTPD), N-isopropyl-N'-phenyl-p-phenylenediamine (IPPD), and N,N'-di-2-naphthyl-p-phenylenediamine (DNPD); quinoline-based antioxidants such as 2,2,4-trimethyl-1,2-dihydroquinoline polymers; monophenol-based antioxidants such as 2,6-di-t-butyl-4-methylphenol and styrenated phenol; and bis-, tris-, and polyphenol-based antioxidants such as tetrakis-[methylene-3-(3',5'-di-t-butyl-4'-hydroxyphenyl)propionate]methane. Among them, p-phenylenediamine-based antioxidants and quinoline-based antioxidants are preferred, and N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine and 2,2,4-trimethyl-1,2-dihydroquinoline polymers are more preferred. Commercially available products include those from Seiko Chemical Co., Ltd., Sumitomo Chemical Co., Ltd., Ouchi Shinko Chemical Co., Ltd., Flexis, and the like.

[0145] In the surface rubber layer composition and the inner rubber layer composition, the content of the antioxidant is preferably 0.5 parts by mass or more, more preferably 1.5 parts by mass or more, and even more preferably 2.0 parts by mass or more, based on 100 parts by mass of the rubber component. The content is preferably 7.0 parts by mass or less, and more preferably 5.0 parts by mass or less.

[0146] The surface rubber layer composition and the inner rubber layer composition preferably contain stearic acid. In the above surface rubber layer composition and the above inner rubber layer composition, the content of stearic acid is preferably 0.5 parts by mass or more, more preferably 2.0 parts by mass or more, and preferably 10 parts by mass or less, more preferably 5 parts by mass or less, per 100 parts by mass of the rubber component.

[0147] As the stearic acid, any conventionally known product can be used, for example, products available from NOF Corp., Kao Corp., Fujifilm Wako Pure Chemical Industries, Ltd., Chiba Fatty Acid Co., Ltd., and the like.

[0148] The surface rubber layer composition and the inner rubber layer composition preferably contain zinc oxide. In the above rubber composition for cap treads, the content of zinc oxide is preferably 0.5 parts by mass or more, more preferably 2.0 parts by mass or more, and preferably 5.0 parts by mass or less, more preferably 3.0 parts by mass or less, per 100 parts by mass of the rubber component.

[0149] As the zinc oxide, any known zinc oxide can be used, for example, products available from Mitsui Mining & Smelting Co., Ltd., Toho Zinc Co., Ltd., Hakusui Tech Co., Ltd., Seido Chemical Industry Co., Ltd., Sakai Chemical Industry Co., Ltd., etc.

[0150] The surface rubber layer composition and the inner rubber layer composition may contain wax. In the above surface rubber layer composition and the above inner rubber layer composition, the wax content is preferably 0.5 parts by mass or more, more preferably 2.0 parts by mass or more, and preferably 10.0 parts by mass or less, more preferably 5.0 parts by mass or less, per 100 parts by mass of the rubber component.

[0151] The wax is not particularly limited, and any wax commonly used in the tire industry can be suitably used. Examples include petroleum wax, mineral wax, synthetic wax, and plant-derived wax. Among them, petroleum wax and plant-derived wax are preferred, and petroleum wax is more preferred. Examples of plant-derived wax include rice wax, carnauba wax, and candelilla wax. Examples of petroleum wax include paraffin wax, microcrystalline wax, and selected special waxes thereof, and paraffin wax is preferred. The wax according to this embodiment does not contain stearic acid. The wax can be, for example, commercially available waxes from Ouchi Shinko Chemical Industry Co., Ltd., Nippon Seiro Co., Ltd., Paramelt Co., Ltd., and the like. These waxes may be used alone or in combination of two or more types.

[0152] The surface rubber layer composition and the inner rubber layer composition each contain sulfur. In the surface rubber layer composition and the inner rubber layer composition, the sulfur content is preferably 0.5 parts by mass or more, more preferably 1.0 parts by mass or more, and even more preferably 1.5 parts by mass or more, based on 100 parts by mass of the rubber component. The content is preferably 3.5 parts by mass or less, more preferably 3.0 parts by mass or less, and even more preferably 2.5 parts by mass or less. Within the above ranges, the effect tends to be better obtained.

[0153] Examples of sulfur include powdered sulfur, precipitated sulfur, colloidal sulfur, insoluble sulfur, highly dispersible sulfur, soluble sulfur, etc., which are commonly used in the rubber industry. Commercially available products include those from Tsurumi Chemical Industry Co., Ltd., Karuizawa Sulfur Co., Ltd., Shikoku Chemical Industry Co., Ltd., Flexis Corporation, Nippon Kanzuri Kogyo Co., Ltd., Hosoi Chemical Industry Co., Ltd., etc. These may be used alone or in combination of two or more kinds.

[0154] The surface rubber layer composition and the inner rubber layer composition preferably contain a vulcanization accelerator. In the rubber composition for cap tread, the content of the vulcanization accelerator is not particularly limited and may be freely determined according to the desired vulcanization speed and crosslink density, but is preferably 1.0 part by mass or more, more preferably 3.0 parts by mass or more, and even more preferably 4.0 parts by mass or more, based on 100 parts by mass of the rubber component. The upper limit is preferably 8.0 parts by mass or less, more preferably 7.0 parts by mass or less, and even more preferably 6.0 parts by mass or less.

[0155] The type of vulcanization accelerator is not particularly limited, and commonly used ones can be used. Examples of the vulcanization accelerator include thiazole-based vulcanization accelerators such as 2-mercaptobenzothiazole, di-2-benzothiazolyl disulfide, and N-cyclohexyl-2-benzothiazyl sulfenamide; thiuram-based vulcanization accelerators such as tetramethylthiuram disulfide (TMTD), tetrabenzylthiuram disulfide (TBzTD), and tetrakis(2-ethylhexyl)thiuram disulfide (TOT-N); sulfenamide-based vulcanization accelerators such as N-cyclohexyl-2-benzothiazole sulfenamide, Nt-butyl-2-benzothiazolyl sulfenamide, N-oxyethylene-2-benzothiazole sulfenamide, and N,N'-diisopropyl-2-benzothiazole sulfenamide; and guanidine-based vulcanization accelerators such as diphenylguanidine, di-orthotolyl guanidine, and orthotolyl biguanidine. These may be used alone or in combination of two or more. Among them, sulfenamide-based, guanidine-based and benzothiazole-based vulcanization accelerators are preferred.

[0156] In addition to the above-mentioned components, the surface rubber layer composition and the inner rubber layer composition may appropriately contain compounding agents generally used in the tire industry, such as materials such as a mold release agent.

[0157] In this specification, various materials containing carbon atoms (e.g., rubber, oil, resin, vulcanization accelerator, antioxidant, surfactant, etc.) may be derived from carbon dioxide in the atmosphere. As a method for obtaining the compound of the present invention from carbon dioxide, carbon dioxide may be directly converted, or methane obtained through a methanation process for synthesizing methane from carbon dioxide may be converted.

[0158] The surface rubber layer composition and the inner rubber layer composition can be produced, for example, by kneading the above-mentioned components using a rubber kneading device such as an open roll or a Banbury mixer, followed by vulcanization.

[0159] As for the kneading conditions, in the base kneading step in which additives other than the crosslinking agent (vulcanizing agent) and the vulcanization accelerator are kneaded, the kneading temperature is preferably 100°C or higher, more preferably 120°C or higher, and also preferably 180°C or lower, more preferably 170°C. In the finish kneading step in which the vulcanizing agent and the vulcanization accelerator are kneaded, the kneading temperature is preferably 80°C or higher, and also preferably 120°C or lower, more preferably 110°C or lower. In addition, the composition kneaded with the vulcanizing agent and the vulcanization accelerator is usually subjected to a vulcanization treatment such as press vulcanization. The vulcanization temperature is preferably 140°C or higher, more preferably 150°C or higher, and also preferably 190°C or lower, more preferably 185°C or lower.

[0160] The acetone extractable amount AE (mass%) of the surface rubber layer composition (rubber composition after vulcanization) is preferably 14.1 mass% or more, more preferably 15.0 mass% or more, even more preferably 18.5 mass% or more, and particularly preferably 20.6 mass% or more. The upper limit of AE is preferably 30.0 mass% or less, more preferably 25.0 mass% or less, and even more preferably 22.0 mass% or less. Within the above range, the effect tends to be preferably obtained.

[0161] Although the mechanism by which the effect is obtained when the acetone extractable content of the surface rubber layer composition is a certain amount or more, particularly 15.0 mass% or more, is not clear, it is considered that the more the acetone extractable content is, the more the dispersion of the lignin-based material and the dispersion of silica are promoted, and therefore the more the effect is likely to be obtained, and therefore it is presumed that the wet performance is significantly improved.

[0162] In this specification, the acetone extractable amount (AE) is a value measured by a method for measuring acetone extractable amount in accordance with JIS K 6229:2015.

[0163] As a method for adjusting the AE, a method known to those skilled in the art can be adopted. For example, the AE tends to increase when the amount of plasticizers such as various oils in the rubber composition increases.

[0164] The tire is manufactured by a normal method using the surface rubber layer composition and the inner rubber layer composition. That is, a composition containing various additives as necessary is extruded in an unvulcanized state to match the shapes of various tire components such as the surface rubber layer and the inner rubber layer, molded in a normal method on a tire building machine, laminated with other tire components to form an unvulcanized tire, and then heated and pressurized in a vulcanizer to manufacture the tire.

[0165] The tire is not particularly limited, and examples thereof include pneumatic tires, solid tires, airless tires, etc. Among these, pneumatic tires are preferred.

[0166] The above tires are suitably used as passenger car tires, large passenger car tires, large SUV tires, truck and bus tires, motorcycle tires, racing tires, winter tires (studless tires, snow tires, studded tires), all-season tires, run-flat tires, aircraft tires, mining tires, etc.

[0167] In the tire, the thickness Tc (mm) of the surface rubber layer is preferably 12.0 mm or less, more preferably 9.6 mm or less, even more preferably 9.0 mm or less, and particularly preferably 8.0 mm or less. The lower limit of the thickness Tc of the surface rubber layer is preferably 4.0 mm or more, more preferably 5.0 mm or more, and even more preferably 5.5 mm or more. In addition, within the above range, the effect tends to be preferably obtained.

[0168] In the tire, the total thickness (mm) of the inner rubber layer is preferably 0.4 mm or more, more preferably 1.0 mm or more, even more preferably 1.5 mm or more, and particularly preferably 2.0 mm or more. The upper limit of the total thickness of the inner rubber layer is preferably 5.0 mm or less, more preferably 4.0 mm or less, and even more preferably 3.0 mm or less. Within the above range, the effect tends to be preferably obtained.

[0169] In the tire, the multi-layered tread portion consisting of the surface rubber layer and at least one inner rubber layer disposed radially inward of the surface rubber layer has a ratio (=total thickness / total thickness×100(%)) of the total thickness (mm) of the inner rubber layer to the total thickness (thickness (mm) of the surface rubber layer+total thickness (mm) of the inner rubber layer) of preferably 10% or more, more preferably 15% or more, and even more preferably 20% or more. The upper limit of this ratio is preferably 50% or less, more preferably 40% or less, and even more preferably 30% or less. When this ratio is above a certain level, fuel efficiency tends to be improved.

[0170] When the above ratio is a certain amount or more, particularly when it is 15% or more, the mechanism by which the above effect is obtained is not clear; however, it is believed that the higher the inner layer ratio, the more the heat generation of the tire is suppressed, resulting in an improvement in fuel efficiency.

[0171] In the tire, the thickness Tb (mm) of the inner rubber layer containing the lignin-based material is preferably 0.3 mm or more, more preferably 0.7 mm or more, even more preferably 1.0 mm or more, and particularly preferably 1.5 mm or more. The upper limit of the thickness Tb (mm) of the inner rubber layer is preferably 4.5 mm or less, more preferably 4.0 mm or less, and even more preferably 3.0 mm or less. Within the above range, the effect tends to be preferably obtained.

[0172] In the tire, the product (Lb×Tb) of the content Lb (parts by mass) of the lignin-based material relative to 100 parts by mass of the rubber component in the composition for the inner rubber layer containing the lignin-based material and the thickness Tb (mm) of the inner rubber layer containing the lignin-based material is preferably 2.5 or more, more preferably 10.0 or more, even more preferably 15.0 or more, and particularly preferably 20.0 or more. The upper limit of Lc / Tc is preferably 40.0 or less, more preferably 25.0 or less, and even more preferably 23.0 or less. Within the above range, the effect tends to be preferably obtained.

[0173] Although the mechanism by which the effect is greater when Lb×Tb is greater than a certain value, especially when it is greater than 2.5, is unclear, it is believed that the stiffness is increased by increasing the thickness of the inner rubber layer containing the lignin-based material, and that the force is more easily transmitted between the rubber layers by compounding a certain amount of lignin-based material or more. Therefore, it is presumed that the steering stability on dry road surfaces is significantly improved.

[0174] In the tire, the product (Sb×Tb) of the content Sb (parts by mass) of silica per 100 parts by mass of the rubber component in the inner rubber layer composition containing the lignin-based material and the thickness Tb (mm) of the inner rubber layer containing the lignin-based material is preferably 10 or more, more preferably 30 or more, even more preferably 50 or more, and particularly preferably 60 or more. The upper limit of Sb×Tb is preferably 100 or less, more preferably 90 or less, and even more preferably 80 or less. Within the above range, the effect tends to be preferably obtained.

[0175] Although the mechanism by which the effect is obtained when Sb×Tb is a certain amount or more, particularly when it is 30 or more, is not clear, it is believed that by compounding a certain amount or more of silica, the silica and the lignin-based material form a network, and the thickness of the inner rubber layer containing the lignin-based material is increased, thereby increasing rigidity. Therefore, it is presumed that the steering stability on dry road surfaces is significantly improved.

[0176] In this specification, the "thickness Tc of the surface rubber layer" refers to the thickness of the surface rubber layer on the tire equatorial plane in the tire radial cross section, and means the linear distance from the tread surface (surface of the surface rubber layer) to the radially inner side surface of the surface rubber layer in the tire radial cross section. The "total thickness of the inner rubber layers" refers to the total thickness of the inner rubber layers consisting of at least one layer on the tire equatorial plane in the tire radial cross section, and means the straight-line distance from the radially inner side surface of the surface rubber layer to the radially inner side surface of the radially innermost rubber layer of the inner rubber layers in the tire radial cross section. "Total thickness of the multilayered tread portion" refers to the total thickness of the multilayered tread portion on the tire equatorial plane in the tire radial cross section, and means the straight-line distance from the tread surface (surface of the surface rubber layer) to the radially inner side surface of the radially innermost rubber layer of the inner rubber layers, specifically, the straight-line distance from the tread surface to the interface of the reinforcing layer containing other fiber materials, such as a belt layer, a carcass layer, etc., on the tire radially outermost surface side. "Thickness Tb of the inner rubber layer containing a lignin-based material" refers to the thickness of each inner rubber layer containing a lignin-based material on the tire equatorial plane in the tire radial cross section, and means the straight-line distance from the tire radial outer surface of each inner rubber layer containing the lignin-based material to the tire radial inner surface of each inner rubber layer containing the lignin-based material in the tire radial cross section.

[0177] "Thickness Tc of the surface rubber layer," "total thickness of the inner rubber layers," "total thickness of the multi-layered tread portion," and "thickness Tb of the inner rubber layer containing a lignin-based material" are values ​​measured on the equatorial plane of the tire along the equatorial plane of the tire. When a current-carrying member or the like is present on the tire equatorial plane, this value is measured along the tire equatorial plane from a straight line connecting the ends of the interfaces blocked by the current-carrying member. When a groove is present on the tire equatorial plane, the thickness is measured at the center in the tire width direction of the land portion closest to the tire equatorial plane, and is the thickness measured in the normal direction of the radially outer surfaces of the surface rubber layer, the inner rubber layer, the multilayered tread portion, and the inner rubber layer containing the lignin-based material.

[0178] In the tire, the groove depth D (mm) of the circumferential groove formed in the multi-layered tread portion is preferably 5.0 mm or more, more preferably 6.0 mm or more, and even more preferably 7.0 mm or more, and is preferably 10.0 mm or less, more preferably 9.0 mm or less, and even more preferably 8.0 mm or less. Within the above ranges, the effect tends to be better obtained.

[0179] The mechanism by which a greater effect is obtained when the groove depth D of the circumferential grooves formed in the tread portion is adjusted within a predetermined range is not clear; however, it is presumed that adjusting the groove depth ensures good rigidity, and as a result, steering stability on dry road surfaces is significantly improved.

[0180] In this specification, the groove depth D of the circumferential groove is measured along the normal to the surface that forms the contact surface of the outermost tread surface, and means the distance from the surface that forms the contact surface to the deepest groove bottom, and refers to the maximum distance among the groove depths of the circumferential grooves provided.

[0181] In the tire, it is desirable that the ratio (Lb / D) of the content Lb (parts by mass) of the lignin-based material per 100 parts by mass of the rubber component in the composition for the inner rubber layer containing the lignin-based material to the groove depth D (mm) of the circumferential groove formed in the multi-layer structure tread portion is 0.5 to 5.0. Lb / D is preferably 0.6 or more, more preferably 0.8 or more, and even more preferably 1.0 or more. The upper limit of Lb / D is preferably 3.0 or less, more preferably 2.5 or less, and even more preferably 2.0 or less. Within the above range, the effect tends to be better obtained.

[0182] Although the mechanism by which a greater effect is obtained when Lb / D is adjusted to 0.5 to 5.0 is unclear, it is believed that adjusting the groove depth ensures good rigidity, and the inclusion of a sufficient amount of lignin-based material makes it easier for force to be transmitted between the rubber layers. Therefore, it is presumed that steering stability on dry road surfaces is significantly improved.

[0183] In the tire, it is desirable that the ratio (Sb / D) of the content Sb (parts by mass) of the silica per 100 parts by mass of the rubber component in the inner rubber layer composition containing the lignin-based material to the groove depth D (mm) of the circumferential groove formed in the multi-layer structure tread portion is 0.5 to 10.0. Sb / D is preferably 2.0 or more, more preferably 3.0 or more, and even more preferably 4.0 or more. The upper limit of Sb / D is preferably 8.0 or less, more preferably 7.0 or less, and even more preferably 6.0 or less. Within the above range, the effect tends to be better obtained.

[0184] Although the mechanism by which the effect is improved when Sb / D is adjusted to 0.5 to 10.0 is unclear, it is believed that the groove depth is adjusted to ensure good rigidity, and the silica and lignin-based material form a network by blending a certain amount of silica or more. Therefore, it is presumed that the wet performance is significantly improved.

[0185] In this specification, dimensions such as thickness are measured with the bead portion of the tire aligned to the standard rim width. During measurement, the tire is cut out in the tire radial direction, and both bead ends of the sample are fixed in a state where they are aligned to the standard rim width.

[0186] In this specification, unless otherwise specified, the dimensions of each part of the tire are values ​​measured under normal conditions. In this specification, the term "normal condition" refers to a condition in which the tire is mounted on a normal rim (not shown), inflated to normal internal pressure, and no load is applied.

[0187] When it is not possible to measure with the tire mounted on a regular rim, the dimensions and angles of each part in the meridian section of the tire are measured by cutting the tire along a plane including the axis of rotation, and the distance between the left and right beads in the cross section is measured so that it corresponds to the distance between the beads of the tire mounted on a regular rim.

[0188] "Genuine rim" refers to the rim that is specified for each tire by the standard system that includes the standard on which the tire is based, for example, "Standard rim" in the applicable size listed in the "JATMA YEAR BOOK" for JATMA (Japan Automobile Tire Manufacturers Association), "Measuring Rim" in the "STANDARDS MANUAL" for ETRTO (The European Tire and Rim Technical Organisation), and "Design Rim" in the "YEAR BOOK" for TRA (The Tire and Rim Association, Inc.). Refer to JATMA, ETRTO, and TRA in that order, and follow the standard if there is an applicable size at the time of reference. In the case of a tire not specified in the standard, it refers to the rim that can be assembled to the rim and can hold internal pressure, that is, the rim with the smallest rim diameter and the next narrowest rim width among the rims that do not leak air from between the rim and tire.

[0189] "Regular internal pressure" refers to the air pressure specified for each tire by each standard in the standard system including the standard on which the tire is based. For JATMA, it refers to the "Maximum Air Pressure", for ETRTO, it refers to the "INFLATION PRESSURE", and for TRA, it refers to the maximum value listed in the table "TIRE LOAD LIMITS AT VARIOUS COLD INFLATION PRESSURES". As with "regular rims", it refers to JATMA, ETRTO, TRA in that order and follows those standards. For tires not specified in the standard, it refers to the regular internal pressure (250kPa or more) of another tire size (specified in the standard) that is specified with the regular rim as the standard rim. Note that if multiple regular internal pressures of 250kPa or more are specified, it refers to the smallest value among them.

[0190] In this specification, the term "normal load" refers to the load that is determined for each tire by each standard in the standard system including the standard on which the tire is based, and is the maximum load capacity in the case of JATMA, the "LOAD CAPACITY" in the case of ETRTO, and the maximum value listed in the table "TIRE LOAD LIMITS AT VARIOUS COLD INFLATION PRESSURES" in the case of TRA. As in the case of the "normal rim" and "normal internal pressure" mentioned above, JATMA, ETRTO, and TRA are referred to in that order and their standards are followed. In the case of a tire not determined by a standard, the normal load W is calculated as follows: L Request. V = {(Dt / 2) 2 -(Dt / 2-Ht) 2}×π×Wt W L =0.000011×V+175 W L :Normal load (kg) V: Virtual volume of the tire (mm 3 ) Dt: Tire outer diameter (mm) Ht: Section height of the tire (mm) Wt: tire section width (mm)

[0191] The "section width Wt (mm)" of a tire is the maximum width between the outer surfaces of the sidewalls when the tire is in its normal condition, excluding any patterns or lettering on the sidewalls.

[0192] The "outer diameter Dt (mm)" of a tire refers to the outer diameter of the tire under normal conditions.

[0193] The "section height Ht (mm)" of a tire refers to the radial height of the tire at its radial cross section, and corresponds to half the difference between the tire's outer diameter Dt and the rim diameter R, where R is the tire's rim diameter (mm). In other words, the section height Ht can be calculated by (Dt-R) / 2.

[0194] An example of a tire according to the present invention will be described below with reference to the drawings, but the present invention is not limited to this embodiment.

[0195] 1, the up-down direction is the radial direction of the tire 2, the left-right direction is the axial direction of the tire 2, and the direction perpendicular to the paper surface is the circumferential direction of the tire 2. The tire 2 is symmetrical. The tread portion 4 (multi-layer structure tread portion) includes a cap layer 30 (surface rubber layer) and a base layer 28 (inner rubber layer). The cap layer 30 is made of the above-mentioned surface rubber layer composition, and the base layer 28 is made of the above-mentioned inner rubber layer composition containing the lignin-based material.

[0196] Although FIG. 1 shows an example of a two-layer tread structure consisting of a cap layer 30 and a base layer 28, a single-layer tread or a tread having a structure of three or more layers may also be used.

[0197] In the tire 2 of FIG. 1, both the cap layer 30 and the base layer 28 contain the lignin-based material. The content Lc (parts by mass) of the lignin-based material per 100 parts by mass of the rubber component of the cap layer 30 is less than the content Lb (parts by mass) of the lignin-based material per 100 parts by mass of the rubber component of the base layer 28 (Lc <Lb)。

[0198] In the tire 2, each sidewall 6 extends substantially radially inward from an end of the tread portion 4. A radially outer portion of each sidewall 6 is joined to the tread portion 4. A radially inner portion of each sidewall 6 is joined to a clinch 10. The sidewalls 6 can prevent damage to the carcass 14.

[0199] 1 is located between the tread portion 4 and the sidewall 6. The wing 8 is joined to each of the tread portion 4 and the sidewall 6.

[0200] Each clinch 10 is located approximately radially inward of the sidewall 6 and has at least one or more portions that come into contact with the rim.

[0201] The carcass 14 includes a carcass ply 36. In the tire 2, the carcass 14 is made up of one carcass ply 36, but may be made up of two or more carcass plies.

[0202] In the tire 2, the carcass ply 36 is laid between the bead cores 32 on both sides and extends along the tread portion 4 and the sidewall 6. The carcass ply 36 is folded back from the inside to the outside in the axial direction around each bead core 32. By this folding back, the carcass ply 36 is formed with a main portion 36a and a pair of folded back portions 36b. That is, the carcass ply 36 has the main portion 36a and a pair of folded back portions 36b.

[0203] Each bead core 32 includes a bead apex 34 extending radially outward from the bead core 32. The bead core 32 is preferably ring-shaped and includes a wound non-stretchable wire. The bead apex 34 tapers radially outward.

[0204] Although not shown, the carcass ply 36 is preferably made of a number of parallel cords and a topping rubber. The absolute value of the angle that each cord makes with respect to the equatorial plane CL is preferably 75° to 90°. In other words, the carcass 14 preferably has a radial structure.

[0205] The belt layer 16 in FIG. 1 is located radially inward of the tread portion 4. The belt layer 16 is laminated with the carcass 14. The belt layer 16 reinforces the carcass 14. In the tire 2 in FIG. 1, the belt layer 16 is composed of an inner layer 38 and an outer layer 40. As is clear from FIG. 1, it is desirable that the width of the inner layer 38 is slightly larger than the width of the outer layer 40 in the axial direction. In this tire 2, the axial width of the belt layer 16 is preferably 0.6 times or more and 0.9 times or less of the cross-sectional width of the tire 2.

[0206] Each of the inner layer 38 and the outer layer 40 is preferably made of a number of parallel single-wire steel cords (steel monofilaments) and a topping rubber (coating rubber). In other words, the belt layer 16 includes a number of parallel steel monofilaments.

[0207] The band 18 in Fig. 1 is located radially outside the belt layer 16. In the axial direction, the band 18 has a width equal to the width of the belt layer 16. The band 18 may also have a width greater than the width of the belt layer 16.

[0208] Although not shown, the band 18 is preferably made of a cord and a topping rubber. The cord is wound in a spiral shape. This band 18 has a so-called jointless structure. The cord extends substantially in the circumferential direction. The angle of the cord with respect to the circumferential direction is preferably 5° or less, and more preferably 2° or less. Since the belt layer 16 is restrained by the cord, lifting of the belt layer 16 is suppressed.

[0209] 1 constitute a reinforcing layer. The reinforcing layer may be constituted by the belt layer 16 alone.

[0210] FIG. 2 is an enlarged cross-sectional view showing the vicinity of the tread portion 4 (multi-layer structure tread portion) in FIG. The tire in FIG. 2 is a tire 2 having a groove 26 on the tire equatorial plane (CL).

[0211] In this case, the thickness Tc of the cap layer 30, the thickness Tb of the base layer 28 (corresponding to the thickness Tb of the inner rubber layer containing a lignin-based material and the total thickness of the inner rubber layers), and the total thickness of the tread portion 4 (total thickness of the multi-layered tread portion) refer to the thicknesses measured at the center in the tire width direction of the land portion closest to the groove 26 on the tire equatorial plane in the radial cross section of the tire, measured in the normal direction to the surfaces of the cap layer 30, the base layer 28, and the tread portion 4. Specifically, the thickness Tc of the cap layer 30 means the linear distance in the normal direction from the outer surface of the cap layer 30 in the tire radial direction to the interface of the base layer 28 on the tire outermost surface side. The thickness Tb of the base layer 28 means the linear distance from the outer surface of the base layer 28 in the tire radial direction to the interface of the band 18 on the tire outermost surface side in the tire radial direction. The total thickness of the tread portion 4 means the straight-line distance from the radially outer surface of the cap layer 30 to the interface of the band 18 on the tire's radially outermost side, and is the sum of the thickness Tc of the cap layer 30 and the thickness Tb of the base layer 28.

[0212] The inner liner 20 is located inside the carcass 14. The inner liner 20 is bonded to the inner surface of the carcass 14. A typical base rubber of the inner liner 20 is butyl rubber or halogenated butyl rubber. The inner liner 20 holds the internal pressure of the tire 2.

[0213] Each chafer 22 is located adjacent to a bead 12. In this embodiment, the chafer 22 is preferably made of fabric with rubber impregnated into the fabric. The chafer 22 may be integral with the clinch 10.

[0214] In this tire 2, the tread portion 4 has main grooves 42 as the grooves 26. As shown in FIG. 1, a plurality of main grooves 42, specifically three main grooves 42, are formed in the tread portion 4. These main grooves 42 are arranged at intervals in the axial direction. In the tread portion 4, four ribs 44 extending in the circumferential direction are formed by forming the three main grooves 42. In other words, the main grooves 42 are formed between the ribs 44.

[0215] Each of the main grooves 42 extends in the circumferential direction. The main grooves 42 are continuous in the circumferential direction without interruption. The main grooves 42 facilitate the drainage of water present between the road surface and the tire 2, for example, in rainy weather. Therefore, even if the road surface is wet, the tire 2 can make sufficient contact with the road surface. 2D indicates the groove depth of the main groove 42 formed in the tread portion 4 in the circumferential direction.

[0216] In tire 2, with respect to the content Lc of the lignin-based material per 100 parts by mass of the rubber component of cap layer 30, the content Lb of the lignin-based material per 100 parts by mass of the rubber component of base layer 28, the thickness Tb of base layer 28, the content Sb of silica per 100 parts by mass of the rubber component of base layer 28, and the groove depth D of the circumferential groove formed in tread portion 4, it is desirable that Lb×Tb, Sc, Tb, Sb×Tb, D, Lb / D, and Sb / D are within the above-mentioned ranges. EXAMPLES

[0217] In the following, examples (embodiments) that are considered to be preferable for carrying out the present invention will be shown, but the scope of the present invention is not limited to the examples.

[0218] The various chemicals used in the production of the cap layer and base layer are described below. If necessary, the chemicals are purified according to standard methods. (Cap layer) NR:TSR20 SBR: SBR1502 manufactured by JSR Corporation (styrene content: 23.5% by mass) BR: BR150B manufactured by Ube Industries, Ltd. (cis content: 96% by mass) Lignin-based materials: Lignosulfonic acid (N2SA: 123 μm 2 / g) Carbon black: Show Black N220 (N2SA:111m) manufactured by Cabot Japan Co., Ltd. 2 / g) Silica: Ultrasil VN3 (N2SA: 175m) manufactured by Evonik Degussa 2 / g) Silane coupling agent: Si266 (bis(3-triethoxysilylpropyl) disulfide) manufactured by Evonik Degussa Resin: SYLVARES SA85 manufactured by Arizona Chemical Company (α-methylstyrene-based resin (copolymer of α-methylstyrene and styrene), softening point 85°C) Oil: H&R Vivatec 500 (TDAE, aromatic process oil) Zinc oxide: Zinc oxide No. 1 manufactured by Mitsui Mining & Smelting Co., Ltd. Anti-aging agent: Antigen 6C (N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine) manufactured by Sumitomo Chemical Co., Ltd. Stearic acid: Camellia made by NOF Corporation Wax: Ozoace 0355 manufactured by Nippon Seiro Co., Ltd. Sulfur: HK-200-5 (powdered sulfur) manufactured by Hosoi Chemical Industry Co., Ltd. Vulcanization accelerator 1: Noccelaer D (N,N'-diphenylguanidine) manufactured by Ouchi Shinko Chemical Industry Co., Ltd. Vulcanization accelerator 2: Noccela CZ-G (N-cyclohexyl-2-benzothiazolyl sulfenamide) manufactured by Ouchi Shinko Chemical Industry Co., Ltd.

[0219] (Base layer) NR:TSR20 BR: BR150B (cis content: 97% by mass) manufactured by Ube Industries, Ltd. Lignin-based materials: Lignosulfonic acid (N2SA: 123 μm 2 / g) Carbon black: Show Black N220 (N2SA:111m) manufactured by Cabot Japan Co., Ltd. 2 / g) Silica: Ultrasil VN3 (N2SA: 175m) manufactured by Evonik Degussa 2 / g) Silane coupling agent: Si266 (bis(3-triethoxysilylpropyl) disulfide) manufactured by Evonik Degussa Zinc oxide: Zinc oxide No. 1 manufactured by Mitsui Mining & Smelting Co., Ltd. Anti-aging agent: Antigen 6C (N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine) manufactured by Sumitomo Chemical Co., Ltd. Stearic acid: Camellia made by NOF Corporation Wax: Ozoace 0355 manufactured by Nippon Seiro Co., Ltd. Sulfur: Powdered sulfur manufactured by Karuizawa Sulfur Co., Ltd. Vulcanization accelerator 1: Noccelaer D (N,N'-diphenylguanidine) manufactured by Ouchi Shinko Chemical Industry Co., Ltd. Vulcanization accelerator 2: Noccela CZ-G (N-cyclohexyl-2-benzothiazolyl sulfenamide) manufactured by Ouchi Shinko Chemical Industry Co., Ltd.

[0220] (Preparation of Rubber Composition for Cap Layer) According to the composition shown in Table 1, materials other than sulfur and vulcanization accelerator are kneaded for 5 minutes at 150° C. using a 1.7 L Banbury mixer manufactured by Kobe Steel, Ltd. to obtain a kneaded mixture. Sulfur and a vulcanization accelerator are added to the kneaded mixture, and the mixture is kneaded for 5 minutes at 80° C. using an open roll to obtain an unvulcanized rubber composition.

[0221] (Preparation of Rubber Composition for Base Layer) According to the composition shown in Table 1, materials other than sulfur and vulcanization accelerator are kneaded for 5 minutes at 150° C. using a 1.7 L Banbury mixer manufactured by Kobe Steel, Ltd. to obtain a kneaded mixture. Sulfur and a vulcanization accelerator are added to the kneaded mixture, and the mixture is kneaded for 5 minutes at 80° C. using an open roll to obtain an unvulcanized rubber composition.

[0222] <Manufacturing method for test tires> According to the specifications in Table 1, the rubber composition for the unvulcanized cap layer is molded into the shape of a cap layer, and the rubber composition for the unvulcanized base layer is molded into the shape of a base layer, and these are bonded together with other tire components on a tire building machine to form an unvulcanized tire. The tire is then vulcanized at 170°C for 10 minutes to produce a test tire (size 205 / 70R15, passenger car tire, Figures 1-2).

[0223] The results are shown in Table 1, which are calculated based on the following evaluation method assuming a test tire obtained from a composition whose formulation and specifications are changed according to Table 1. The reference comparative examples are as follows. Table 1: Comparative Example 3

[0224] <Acetone extractables (AE)> A rubber test piece is taken from inside the cap layer of the test tire. The amount of material extracted by acetone contained in the rubber test piece is measured according to the acetone extractable amount measurement method in accordance with JIS K 6229. Acetone extractable amount AE (mass%) = (mass of sample before extraction - mass of sample after extraction) / mass of sample before extraction × 100

[0225] <Steering stability on dry roads> The test tires are fitted to all wheels of a domestic FF2000cc vehicle, and the dry driving stability is evaluated by the driver on a test course (on dry roads) through a sensory evaluation. The standard comparative example is expressed as an index of 100, and the higher the index, the better the driving stability on dry roads.

[0226] [Table 1]

[0227] The present invention (1) is a tire having a multi-layered tread portion including a surface rubber layer and at least one inner rubber layer disposed radially inward of the surface rubber layer, the surface rubber layer and at least one of the inner rubber layers contain a lignin-based material; The tire has a content Lc (parts by mass) of the lignin-based material per 100 parts by mass of the rubber component of the surface rubber layer that is less than a content Lb (parts by mass) of the lignin-based material per 100 parts by mass of the rubber component of the inner rubber layer that contains the lignin-based material.

[0228] The present invention (2) is the tire according to the present invention (1), wherein the lignin-based material contains at least one selected from the group consisting of lignin and lignin derivatives.

[0229] The present invention (3) is characterized in that the inner rubber layer containing the lignin-based material is Contains isoprene rubber, and The tire according to the present invention (1) or (2), wherein the content Lb of the lignin-based material per 100 parts by mass of the rubber component is 3 parts by mass or more.

[0230] The present invention (4) is a tire in any combination with any of the present inventions (1) to (3), in which the product (Lb×Tb) of the content Lb (parts by mass) of the lignin-based material per 100 parts by mass of the rubber component of the inner rubber layer containing the lignin-based material and the thickness Tb (mm) of the inner rubber layer containing the lignin-based material is 2.5 or more.

[0231] The present invention (5) is a tire in any combination with any of the present inventions (1) to (4), wherein the surface rubber layer has a silica content Sc of 30 parts by mass or more per 100 parts by mass of the rubber component.

[0232] The present invention (6) is a tire in any combination with any of the present inventions (1) to (5), wherein the surface rubber layer has an acetone extractable amount AE of 15.0 mass % or more.

[0233] The present invention (7) is a tire in any combination with any of the present inventions (1) to (6), in which the ratio of the total thickness of the inner rubber layer to the total thickness (100%) of the multi-layered tread portion is 15% or more.

[0234] The present invention (8) is a tire in any combination with any of the present inventions (1) to (7), in which the thickness Tb of the inner rubber layer containing the lignin-based material is 1.0 mm or more.

[0235] The present invention (9) is a tire in any combination with any of the present inventions (1) to (8), in which the product (Sb×Tb) of the content of silica Sb (parts by mass) per 100 parts by mass of the rubber component of the inner rubber layer containing the lignin-based material and the thickness Tb (mm) of the inner rubber layer containing the lignin-based material is 30 or more.

[0236] The present invention (10) is a tire in any combination with any of the present inventions (1) to (9), wherein the groove depth D of the circumferential grooves formed in the multilayer structure tread portion is 5.0 to 10.0 mm.

[0237] The present invention (11) is a tire in any combination with any of the present inventions (1) to (10), in which the ratio (Lb / D) of the content Lb (parts by mass) of the lignin-based material per 100 parts by mass of the rubber component of the inner rubber layer containing the lignin-based material to the groove depth D (mm) of the circumferential groove formed in the multilayer structure tread portion is 0.5 to 5.0.

[0238] The present invention (12) is a tire in any combination with any of the present inventions (1) to (11), in which a ratio (Sb / D) of a silica content Sb per 100 parts by mass of the rubber component of the inner rubber layer containing the lignin-based material to a groove depth D (mm) of a circumferential groove formed in the multilayer structure tread portion is 0.5 to 10.0. [Explanation of symbols]

[0239] 2 Tires 4 Tread section (multi-layered tread section) 6 Sidewall 8 Wing 10 Clinch 12 Beads 14 Carcass 16 Belt Layer 18 Bands 20 Inner Liner 22 Chafer 24 Tread Surface 26 Groove 28 Base Layer 30 Cap Layer 32 Bead core 34 Bead Apex 36 Carcass ply 36a Main part 36b Folded part 38 Inner layer 40 outer layer 42 Main groove 44 Ribs CL Tire equatorial plane Tc cap layer thickness Thickness of Tb base layer D Groove depth of the circumferential main groove formed in the multi-layered tread

Claims

1. A tire having a multi-layered tread portion including a surface rubber layer and at least one inner rubber layer disposed radially inward of the surface rubber layer, the surface rubber layer and at least one of the inner rubber layers contain a lignin-based material; A tire in which a content Lc (parts by mass) of the lignin-based material per 100 parts by mass of the rubber component of the surface rubber layer is less than a content Lb (parts by mass) of the lignin-based material per 100 parts by mass of the rubber component of an inner rubber layer containing the lignin-based material.

2. The tire according to claim 1 , wherein the lignin-based material comprises at least one selected from the group consisting of lignin and lignin derivatives.

3. The inner rubber layer containing the lignin-based material is Contains isoprene rubber, and The tire according to claim 1, wherein a content Lb of the lignin-based material per 100 parts by mass of the rubber component is 3 parts by mass or more.

4. 2. The tire according to claim 1, wherein the product (Lb x Tb) of a content Lb (parts by mass) of the lignin-based material per 100 parts by mass of a rubber component of the inner rubber layer containing the lignin-based material and a thickness Tb (mm) of the inner rubber layer containing the lignin-based material is 2.5 or more.

5. The tire according to claim 1, wherein the surface rubber layer has a silica content Sc of 30 parts by mass or more per 100 parts by mass of the rubber component.

6. The tire according to claim 1 , wherein the surface rubber layer has an acetone extractable amount AE of 15.0 mass % or more.

7. 2. The tire according to claim 1, wherein a ratio of a total thickness of the inner rubber layer to a total thickness of the multi-layered tread portion is 15% or more.

8. The tire according to claim 1, wherein the inner rubber layer containing the lignin-based material has a thickness Tb of 1.0 mm or more.

9. 2. The tire according to claim 1, wherein a product (Sb×Tb) of a content Sb (parts by mass) of silica per 100 parts by mass of a rubber component of the inner rubber layer containing the lignin-based material and a thickness Tb (mm) of the inner rubber layer containing the lignin-based material is 30 or more.

10. The tire according to claim 1, wherein a groove depth D of the circumferential groove formed in the multilayer structure tread portion is 5.0 to 10.0 mm.

11. 2. The tire according to claim 1, wherein a ratio (Lb / D) of a content Lb (parts by mass) of the lignin-based material per 100 parts by mass of a rubber component of the inner rubber layer containing the lignin-based material to a groove depth D (mm) of a circumferential groove formed in the multilayer structure tread portion is 0.5 to 5.

0.

12. The tire according to claim 1, wherein a ratio (Sb / D) of a silica content Sb per 100 parts by mass of a rubber component of the inner rubber layer containing the lignin-based material to a groove depth D (mm) of a circumferential groove formed in the multilayer structure tread portion is 0.5 to 10.0.